A vision-based dual-modal system for adjusting the orientation and plant spacing of ginger with biharmonic depth completion and rapid hand–eye calibration - Shuxiang He; Lin Liu; Yihe Zhang; Jin Cheng; Yuhua Li; Jialin Hou; Rui Hou; Kai Zhou (Computers and Electronics in Agriculture, 2026)

Efficient bioleaching of high-magnesium low-grade copper-nickel sulfide ore: optimization and mechanisms - Duo-Rui Zhang; Dai-Ying Wei; Jing Zhang; Hong-Rui Chen; Zi-Jie Jin; Lei Zheng (Minerals Engineering, 2026)

Porosity inversion and determination in gob unconsolidated materials based on acoustic signal response - Shuai-Jing Ren; Le-Xiang-Qian Zhang; Jun Deng; Jin-Rui Wang; Cai-Ping Wang; Yang Xiao; Fu-Ru Kang; Hai-Jian Li; Long-Hui Dou (Fuel, 2026)

Endogenous 6-phospho-β-glucosidase overexpression in Lactiplantibacillus plantarum modulates selective enrichment of bioactive and volatile metabolites in black tea extract - Yao-Zeng Zhang; Zhi-Peng Cheng; Pei-Yi Feng; Xin-Xin Liu; Rui-Shan Liu; Zhen-Ming Lu; Li-Juan Chai; Hong-Yu Xu; Jin-Song Shi; Xiao-Juan Zhang; Zheng-Hong Xu (Food Microbiology, 2026)

Perillaldehyde reduces mitochondrial oxidative stress damage by regulating KCNT2/NR1D1 protein activity in vascular dementia rats - Qian-qian Wang; Hong-dou Zhang; Pei-yao Liu; Chun-rui Zhang; Bao-yue Cui; Xi-yue Li; Meng-yao zhao; Jin-he Yang; Peng Li; Ya-ling Yin; Xue-yu Sun (Molecular Biology Reports, 2026)

Long-term cattle manure application rebuilds topsoil buffering capacity and mitigates fertilizer-induced acidification in Mollisols - Yafei Su; Wenbin Bao; Zhenhua Yu; Xiaojing Hu; Changkai Liu; Rui Fang; Junjie Liu; Jian Jin; Guanghua Wang; Xingyi Zhang; Yuriy Kravchenko; Xiaobing Liu; et al. (Agriculture, Ecosystems & Environment, 2026)

Cuproptosis in hepatocellular carcinoma: bridging copper homeostasis with therapeutic horizons - Songsong Fan; Aoqing Wang; Rui Peng; Jun Cao; Daoyuan Tu; Bingbing Su; Jiahao Zhang; Shengjie Jin; Guoqing Jiang; Chi Zhang; Dou-Sheng Bai (Molecular Biology Reports, 2026)

Recent progress on biological control of Fusarium wilt in vegetable crops - Feng Xiong; Mingfeng Guo; Yawen Liu; Xiaochen Liu; Jiahui Fu; JunZhu Gao; Man Yang; Rui Ma; Tingyu Zhang; Xuesheng Liu; Yu Jin; Juanjuan Qu (Crop Protection, 2026)

Safety and efficacy of recombinant botulinum toxin type A (Eveotox®) in patients with post-stroke upper limb spasticity: Results from a Phase Ib/II clinical trial - Rongrong Lu; Lingjing Jin; Jianzhong Xiong; Lixin Zhang; Yaling Liu; Leilei Xu; Rui Wu; Jianhua Tang; Liandong Zhao; Lihua Dong; Weifeng Luo; Yu Pan; et al. (Toxicon, 2026)

Vegetation conversion and microtopography jointly regulate soil microbial necromass in floodplain wetlands - Xiaomin Zhang; Yakov Kuzyakov; Rui Su; Siwen Hu; Qinglong L. Wu; Dayong Zhao; Jin Zeng (CATENA, 2026)

Automatic identification of ice-snow-water contaminants on airport pavements using 1D self-attention CNN - Jinzhong Zhao; Jin Wu; Rui Zhang; Xiaoxia Lu; Xiangyu Wang; Zhehong Zeng (Cold Regions Science and Technology, 2026)

Aluminum mineral transformation drives reacidification and metal remobilization in a neutralized acidic pit lake - Junyi Gu; Lu Zhang; Ziyi Li; Rui Deng; Zijie Yu; Bo Wang; Zhengbo Yue; Jin Wang (Water Research, 2026)

A multiomics perspective on ecological toxicity, environmental behavior, and synthetic microbiome restoration of RDX in soil - Xu Yang; Xiao-hui Ji; Chen Li; Sheng-rui Zhang; Jin-long Lai; Yu Zhang; Xue-gang Luo (Journal of Environmental Chemical Engineering, 2026)

Effect of liquefaction solvent, catalyst sulfidation method and H2S on mild liquefaction behaviors of Jiangna coal over Fe-based catalysts - Jiaqi Yu; Yuxin Wen; Shuo Wang; Rui Zhang; He Yang; Yang Li; Xingxing Xiao; Yining Guan; Haoquan Hu; Lijun Jin (Fuel, 2026)

Simultaneous extraction of keratin and gelatin from eggshell membrane via a one-step alkali method: Structural features and functional characterization - Yanli Guo; Xinyi Ju; Rui Chuang; Huajiang Zhang; Lina Xu; Lei Jin; Ning Xia; Tong Zhang; He Zhang (Food Chemistry, 2026)

Rapid inverse design of double-curved beams for multi-stable metamaterials based on prescribed deformation histories through artificial neural network - Chun-Zheng Zhao; Xin Wang; Rui Zhang; Yongfeng Jiang; Haibo Ji; Zhen Li; Bingyang Li; Pengfei Wang; Feng Jin; Tian Jian Lu (Engineering Structures, 2026)

Impacts of engineering activities on the permafrost environment in the Hola Basin in the Northern Da Xing'anling Mountains in Northeast China - Hongwei Wang; Xiaoying Li; Ruixia He; Juan Zhang; Wenhui Wang; Yuan Qi; Jinlong Zhang; Rui Yang; Yan Li; Xiaoying Jin; Shuai Huang; Jianjun Tang; et al. (Engineering Geology, 2026)

Mechanobiological antagonism of integrin β1/β3 gates YAP-driven reactionary dentinogenesis through fluid shear stress sensing - Peiqi Liu; Hui Zhang; Haoyu Wang; Jingning Gou; Lingxiang Lian; Bilun Jin; Yi Guo; Wei Gong; Chenxu Wang; Yijie Wang; Rui Zou; Bo Cheng; et al. (Chemical Engineering Journal, 2026)

Ecological risk assessment of 1,4-thioxane and its remediation by a synthetic microbiome based on a sulfur transformation system: From multi-omics to water application - Xu Yang; Ai-de Peng; Yong-han Huang; Jia-hao Cheng; Hao-tian Zhong; Hai-tang Zhou; Pei-qi Liu; Xiao-hui Ji; Chen Li; Sheng-rui Zhang; Jin-long Lai; Xue-gang Luo (Water Research, 2026)

Quantitative decoupling of the key factors and mechanisms of Fenton-pretreated membrane fouling mitigation via machine learning-assisted causal inference - Haoxue Ran; Rui Miao; Jin Zhao; Huihui Zhang; Siyu Wang; Jiayi Zhang; Pei Wang; Lei Wang; Jianqi Yin (Water Research, 2026)

Corrigendum to “Evaluation of street-scale air pollution using multi-source data fusion” [Sustainable Cities and Society 148 (2026) 107644] - Zhihao Guo; Xun Zhang; Zongning Wu; Rui Zhou; Xiansheng Liu; Jin Zou (Sustainable Cities and Society, 2026)

Evaluation of street-scale air pollution using multi-source data fusion - Zhihao Guo; Xun Zhang; Zongning Wu; Rui Zhou; Xiansheng Liu; Jin Zou (Sustainable Cities and Society, 2026)

Ecotoxicological impacts of TNT and its key transformation intermediates in freshwater microcosms and their effective remediation by a bicarbonate-activated peroxide system - Xu Yang; Xiao-hui Ji; Chen Li; Sheng-rui Zhang; Jin-long Lai; Xue-gang Luo; Yong-bing Zhu; San-ping Zhao (Journal of Water Process Engineering, 2026)

A synthetic microbiome drives a multi-omics response to remediate 1,4-dithiane–contaminated soil and simultaneously suppresses antibiotic resistance genes - Xu Yang; Xiao-hui Ji; Chen Li; Sheng-rui Zhang; Jin-long Lai; Xue-gang Luo (Journal of Hazardous Materials, 2026)

Environmentally relevant imidacloprid exposure elicits hippocampal microglial apoptosis via JNK-FOXO3 pathway: Implication for latent central neurotoxicity - Xinyi Wen; Meiyan Li; Zhongyuan Zhang; Jingwen Wang; Hao Hu; Weihong Wang; Jing Jin; Kairong Wang; Jian Sun; Rui Zhang (Journal of Hazardous Materials, 2026)

A Porous Zn-Salen-Based Organic Ionic Polymer as a Robust Bifunctional Catalyst for CO2 Fixation via Epoxide Cycloaddition - Guo-Ling Li; Rui-Yao Qin; Meng-Meng Wang; Qing Li; Shijian Lu; Jin-Shui Su; Qi Zhang; Yun Zhao; Ran Zhang; Zhong-Hai Ni (Journal of Environmental Chemical Engineering, 2026)

Tailoring polyhydroxybutyrate by molecular weight regulation: Green synthesis, food-grade performance and innovative ketogenic applications - Jin Hui Xie; Jia Ying Xin; Yan Wang; Li Rui Sun; Hai Xin Bi; Jian Xiong Zhang; Chun Gu Xia (Food Research International, 2026)

The gut microbial metabolism of structurally varied procyanidin oligomers: Focus on metabolites and their characteristics - Chunyi Liu; Ruonan Liu; Qun Lu; Mo Zhang; Xiang Liu; Xiue Jin; Rui Liu (Food Bioscience, 2026)

Decoding the survival strategy of Parachlorella sp. MP1: Genomic basis and physiological adaptations to acidity and heavy metals in acid mine drainage - Meichen Wang; Lu Zhang; Zhengbo Yue; Zijie Yu; Rui Deng; Jin Wang (Bioresource Technology, 2026)

PTPσ mediates the integration of grafted neuronal tissueoids with host neural pathways after complete spinal cord injury - Rui Mao; Yuan-Huan Ma; Jin-Yuan Xiao; Qing-Shuai Wei; Yin-Chun Zhao; Qi-Xing Hu; Hou-Ge Li; Ke-Jun Zhang; Lai-Jian Wang; Hui-Juan Shi; Li-Zhi Peng; Jun-Hua Wang; et al. (Science China Life Sciences, 2026)

A legacy pollutant deciphered by multiomics toxicology and targeted remediation by a synthetic microbial consortium: a case study of 2-chloroacetophenone from abandoned chemical weapons - Xu Yang; Ai-De Peng; Jia-Hao Cheng; Yong-Han Huang; Hao-Tian Zhong; Hai-Tang Zhou; Pei-Qi Liu; Xiao-Hui Ji; Chen Li; Sheng-Rui Zhang; Jin-Long Lai; Xue-Gang Luo; et al. (Water Research, 2026)

Trade-off mechanisms between N2O emissions and nitrogen multifunctionality in a lake littoral mesocosm wetland under seasonal water-level fluctuations: insights from metagenomics and machine learning - Rui Su; Dayong Zhao; Xiaomin Zhang; Qinglong L. Wu; Jin Zeng (Water Research, 2026)

Shifting the processing boundary: On-Farm Pulsed Electric Field Intervention (OFPI) for proactive bioburden reduction and functionalization of raw milk - Bing Yan; Lang-Hong Wang; Jin-Lin Cai; Xiao-Jun Zhang; Cai-Yun Wang; Jian Li; Rui Wang; Xin-An Zeng; Jian He (Trends in Food Science & Technology, 2026)

Differential volatile-omics analysis for tamarind (Tamarindus indica L.) and aroma-active compounds identification via DMU-SPME-GC-MS method - Rui-Hua Jin; Ling Zhang; Li-Bo Qi; Chun-Mei Yuan; Zi-Bo Song; Jia-Teng Chen; Ming Du; Xian-Bing Xu (Food Chemistry, 2026)

Mechanistic study on direct oxidation of xylose to xylonic and xylaric acids in base-free medium - Yinghao Wang; Wei Yu; Zhaozhe Li; Rui Min; Wenmao Zhang; Chunmei Li; Feng Du; Wenjuan Yan; Xin Jin; Chaohe Yang (Chemical Engineering Journal, 2026)

Analysis of Arbuscular Mycorrhizal Fungal Community in Soil of Sugarcane at Different Tillage Depths - Qun-Qing Huang; Sheng Wang; Ying-Jie Nong; Kai-Mao Zhong; Yi-Cheng Su; Xiao-Juan Qin; Jin-Lian Zhang; Yi-Hao Kang; Ting-Su Chen; Shi-Yuan Zeng; Xi-Chao Deng; Ming-Guo Jiang; et al. (Sugar Tech, 2026)

From Lab to Farm: A Low‐Cost Naked‐Eye On‐Site Detecting Platform for Cynoglossus semilaevis Parvovirus Based on Magnetic Beads Adsorption and LAMP ‐ HNB - Shu‐Xia Xue; Si‐Yu Yang; Meng‐Han Xu; Xin‐Rui Liu; Ye‐Xuan Liu; Zi‐Tong Li; Yi‐Xuan Li; Jia‐Ru Hu; Li‐Xian Huang; Xin‐Yi Zhang; Chang Lu; Yu‐Ru Liu; et al. (Journal of Fish Diseases, 2026)
Cynoglossus semilaevis parvovirus (CsPV) is an important pathogen that poses a serious threat to the aquaculture industry. In the absence of vaccines and effective therapeutic drugs, early and sensitive detection of the pathogen is the key measure to prevent and control the outbreaks and epidemics of viral diseases. Currently, the existing detection methods for CsPV are expensive and rely on specialized operations, limiting the application of on‐site detection. There is an urgent need for a low‐cost, user‐friendly detecting platform to prevent fish viral diseases. In this study, we confirmed skin mucus as a target tissue for non‐lethal sampling, established a simple proteinase K digestion, 2% CTAB lysis and silica‐hydroxylated magnetic beads adsorption method for extracting viral genomic DNA from skin mucus and developed a visual one‐pot loop‐mediated isothermal amplification (LAMP) detection method with a sensitivity of 4.69 × 10 1 copies/μL. Validation of the detection platform using clinical samples showed 97% sensitivity and 100% specificity. The cost of reagents for per sample was reduced from 16.6 CNY to 6.2 CNY. The low‐cost naked‐eye on‐site detection platform provides technical support for resource‐limited aquaculture farms to prevent and control emerging viral diseases in Chinese tongue sole.

Integrative multi-omics reveals NQO1-mediated airway epithelial injury as a key mechanism of bisphenol A–induced COPD - Rui Li; Shaobo Ge; Jin Liu; Yuer Li; Shiyuan Yao; Shuhan Ma; Yuanliang Sun; Xiao Li; Xia Yang; Jie Zhang; Ming Zhang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Preparation and characterisation of two new malonylated rare ginsenosides by acid hydrolysis and their anti-hepatoma activities - Ya-Qian Lu; Xiao-Man Jin; Fu-Rui Zhang; Mei-Hui Li; Wen-Wen Li; Wei Li; Chun-Su Yuan; Zhi Liu (Natural Product Research, 2026)

Non-nitrogen-fixing halophytes alleviate nitrogen limitation and decrease soil salinity through nitrogen transfer from nitrogen-fixing plants - Zehao Zhang; Tian Li; Yao Zhang; Rui Hu; Jiabao Li; Hongxiang Jin; Ying Fang; Zhaohua Lu; Jingkuan Sun (Plant and Soil, 2026)

Can urbanization alleviate rural energy poverty? Evidence from China - Boyu Jin; Rui Shi; Chen Zhang; Beibei Lu; Minjuan Zhao (Environment, Development and Sustainability, 2026)

An Integrated GPU‑Accelerated Framework for Closed‑Loop Generation of 3D Morphology–Meso‑mechanics Coupled Random Fields of Rock Particles - Jianqing Jiang; Junjie Zheng; Jin Chang; Shilin Luo; Rui Zhang; Shi Zuo (Rock Mechanics and Rock Engineering, 2026)

Single-cell transcriptomic analysis identifies a MIF-driven keratinocyte-macrophage-Th2 axis as a key inflammatory circuit in atopic dermatitis - Yan Wei; Rui-Min Bai; Hao-Ran Guo; Jin Shan; Li-Juan Wang; Yan Zhou; Kuan-Hou Mou; Yan Zheng; Ya-Guang Zhang (Inflammation Research, 2026)

Enhanced dimethylsulfide emissions following eutrophication remediation in a coastal bay: biogeochemical and hydrological controls - Xiao-Ran Li; Jin-Wei Wu; Xiao-Song Zhong; Hao Qiao; Shi-Bo Yan; Feng Xu; Yu-Cheng Jiang; Rui-Te Zhang; Yu-Hao Qiu; Hong-Hai Zhang (Progress in Oceanography, 2026)

Effects of volcanic altitudes on the rhizosphere microbial community composition and structure of Euphorbia maculata - Yaozhou Zhang; Han Lin; Qixiu Cheng; Haining Wang; Yiming Zhang; Yueming Bao; Rui Qin; Xiaoyu Li; Jin Chen (Physiological and Molecular Plant Pathology, 2026)

Distributed nonlinear placement problems in the NASVs with nonsmooth objectives and unknown time-varying actuator faults - Wen-Jin Liu; Rui-Qi Cao; Xinxin Zhang; Xiang-Yu Yao; Ming-Feng Ge (Ocean Engineering, 2026)

Environmental cadmium drives placental senescence and fetal growth restriction via activating CLPP-dependent mitochondrial stress - Rui Pan; Jin Zhang; Lan-Lan Wu; Cheng-Fang Sun; Xin-Xin Zhang; Yu-Xi Wu; Xu-Ai Yin; Ye-Xin Luo; Si-Ting Liu; Zi-Jian Bao; Wei Chang; Ling-Li Zhao; et al. (Journal of Hazardous Materials, 2026)

Rhizosphere sediments of Phragmites australis harbor elevated genetic potential for microbially mediated biogeochemical cycling and functional redundancy in lakeside wetlands - Hongjie Zhang; Rui Huang; Xiaowei He; Shuwen Xiao; Jin Zeng; Dayong Zhao (Journal of Environmental Sciences, 2026)

Insight into the mechanism of hydrogen transfer and exchange in direct liquefaction of Shangwan coal using isotope-tracer method - Rui Zhang; Lijun Jin; Jianli Wang; Haoquan Hu (Fuel, 2026)

Corrigendum to “Preparation of multifunctional hydrogel composed of polyvinyl alcohol/ chitosan/cellulose nanofiber/anthocyanin and its application in intelligent food packaging systems” [Food Res. Int. 235 (2026) 119173] - Zhen-Zhen Lu; Jie Chen; Jing Jin; Xiao-Rui Ge; Xiao-Hui Yao; Wei-Guo Zhao; Dong-Yang Zhang (Food Research International, 2026)

Preparation of multifunctional hydrogel composed of polyvinyl alcohol/ chitosan/cellulose nanofiber/anthocyanin and its application in intelligent food packaging systems - Zhen-Zhen Lu; Jie Chen; Jing Jin; Xiao-Rui Ge; Xiao-Hui Yao; Wei-Guo Zhao; Dong-Yang Zhang (Food Research International, 2026)

Unveiling varietal specificity in non-destructive grape quality monitoring: Explainable AI and feature selection for sugar and organic acid prediction using NIR spectroscopy - Shijie Shi; Nina Tian; Qi Liu; Rui Yan; Liying Huang; Zhaoqiang Jin; Ke Liu; Xiaohai Tian; Yunbo Zhang (Food Research International, 2026)

Pediococcus pentosaceus JNL0053 Mitigates DSS-induced Colitis in Mice Via the IL-22–Gut Barrier Pathway - Shujun Liu; Huijiao Zhang; Changzhong Jin; Xianbo Geng; Rui Li; Nanping Wu; Yanbo Wang (Probiotics and Antimicrobial Proteins, 2026)

An approach for detecting hemodynamic parameters in the carotid arterial system based on the priori relationship between blood pressure and arterial radius - Jin Wang; Yong-Jiang Li; Yu-Yuan Zhang; Jing-Rui Gu; Xian-Wei Wang; Dong Chen; Kai-Rong Qin (Medical & Biological Engineering & Computing, 2026)

Differential analysis of lipid profiles in natural Calculus Bovis and Bovis Calculus Sativus by UHPLC-MS/MS - Qiang Mao; Huan Zhong; Wan-Li Liang; Jin Dai; Rui-Ting Huang; Yi-Di Wang; Di-Yang Sun; Kai Tang; Long-Fei Xia; Hai-Biao Gong; Yi-Fang Li; Wan-Yang Sun; et al. (Journal of Natural Medicines, 2026)

Modeling hiking speed via interpretable machine learning: Uncovering nonlinear impacts of multidimensional environmental factors - Hao Huang; Jin Yeu Tsou; Hao Zheng; Rui Ma; Haochen Shi; Botao Zhang (Applied Geography, 2026)

Landfill leakage location based on an induced polarization method - Yayu Chen; Shibin Liu; Chaozhi Cai; Weimin Zhang; Hongzhuo Jin; Suxian Zhao; Junfeng Shen; Rui Wang (Environmental Monitoring and Assessment, 2026)

In-situ monitoring reveals the determinants of dissolved methane concentrations within seagrass meadows in a lagoon in northern China - Rui Jin; Xiaoyong Duan; Ping Yin; Xue Li; Bin Chen; Ke Cao; Shenghua Lv; Daolai Zhang; Xingliang He; Xianguo Li; Dahai Zhang (Acta Oceanologica Sinica, 2026)

SYVN1-provoked RASA1 ubiquitination promotes pulmonary inflammation in chronic obstructive pulmonary disease - Ju-Hong Wu; Yi-Cheng Ma; Yu-Qi Wang; Hai-Long Miao; Meng-Xue Liu; Dong-Xu Hua; Min-Min Tang; Tian-Rui Sui; Zhi-Yong Wu; Yu Wang; Jin Yang; Hui Zhao; et al. (Inflammation Research, 2026)

One city, two heats: An LLM-enabled comparative analysis of heat perception, thermal environment, and health pathways in Beijing, China - Jiaqi Zhang; Weijing Wang; Jin Rui; Ziwen Sun (Sustainable Cities and Society, 2026)

A Ca-MOF@COF composite and its in situ grown gel membrane for highly efficient capture of Cd2+ - Xue-Mei Liu; Chuang-Chuang Zhang; Kun Yang; Wei-Liang Jin; Guan-Lian Mo; Rui Liu; Hong-Xin Jiang; Hao-Jie Cui; De-Ming Kong (Journal of Cleaner Production, 2026)

Genome-wide association study of wheat (Triticum aestivum L.) starch pasting properties - Jiahui Jiang; Hao Chang; Yongji Ma; Rui Jin; Rui Yu; Zhenhua Lu; Tianqi Bai; Yufeng Xu; Ruili Gou; Chengyu Lian; Wenting Zhang; Yingang Hu; et al. (Journal of Cereal Science, 2026)

Zircon U-Pb dating and geochemistry of the Paleoproterozoic tuffs from the Nsama formation in northeastern Zambia - Jun-ping Ren; A-lei Gu; Hong-wei Sun; Li-bo Zuo; Jie Wang; Bao-jin Zhao; Evaristo Kasumba; Shi Xing; Zi-jiang Liu; Jin-meng Dong; Jin-rui Zhang; Ji-hai Chen (Journal of African Earth Sciences, 2026)

Cellulose nanocrystal-based antimicrobial porous foam loaded with cinnamaldehyde for enhanced chilled meat preservation - Jin-ling Wu; Ai-ling Zhong; Rui Zhang; Hai-yan Huang; Teng-gen Hu; Zhen-lin Xu; Hong Wang; Peng Wen (Food Packaging and Shelf Life, 2026)

Antimony precipitation processes of orogenic and magmatic-hydrothermal gold‑antimony systems in the West Qinling Orogen, China - Lian Zhang; Hao-Cheng Yu; Jie Wang; Rui Zhu; Lei Wang; Deng-Yang He; Jin-Hong Qiu; Jia-Hui Zhou; Kun-Feng Qiu (Chemical Geology, 2026)

Impacts of different physics schemes on hurricane forecasting in the unified forecast system (UFS) - Linlin Pan; Kathryn Newman; Mrinal Biswas; Brianne Nelson; Bin Liu; Zhan Zhang; Xuejin Zhang; Shuanglong Jin; Zongpeng Song; Rui Hu; Shuanglei Feng; Bo Wang; et al. (Atmospheric Research, 2026)

Enhancing photosynthesis and stress tolerance of the cyanobacterium Nostoc sphaeroides by adaptive laboratory evolution via dry-wet cycles - Zhen Chen; Rui Liu; Yu-Qing Peng; Zhang-Zhuo-Ya Wang; Yong-Qi Yin; Sheng Du; Yu-Jie Jin; Kui Xu; Fei-Fei Li; Wei-Zhi Li; Shan Zhang; Hua-Hua Yue; et al. (Algal Research, 2026)

Oil Slick Detection in X-Band Marine Radar Imagery: Leveraging a Boundary-Aware SBR Feature and an Improved Whale Optimization Algorithm - Jianxun Rui; Jin Xu; Jianbin Yuan; Zekun Guo; Shuo Zhang; Yiteng Zhang; Qiuyu Fu; Boxi Yao; Yulong Yang; Wenhui Li (Journal of Marine Science and Engineering, 2026)
Marine oil spills pose a persistent threat to marine ecosystems and coastal economies, and their rapid and unpredictable spread requires timely and reliable monitoring. In X-band marine radar images, oil slicks usually appear as low-contrast dark targets embedded in heterogeneous sea clutter, making accurate segmentation particularly challenging. To address this problem, this study proposes a training-free two-stage oil slick detection framework that combines an improved Slick Boundary Ratio (SBR) feature with an improved Whale Optimization Algorithm (WOA). First, the improved SBR feature is used to extract the oil slick region of interest (ROI). Then, the improved WOA is employed to determine the global threshold for oil slick segmentation. Experimental results show that the proposed method achieves accurate and spatially coherent oil slick segmentation in complex radar backgrounds, with an Accuracy of 99.36%, a Precision of 85.73%, a Recall of 84.42%, an F1-score of 85.07%, and an Intersection over Union (IoU) of 74.01%. These results indicate that the proposed framework can effectively suppress false positives while maintaining strong detection sensitivity, thereby improving segmentation robustness in low-contrast marine radar scenes. Owing to its training-free design, the proposed method shows potential for shipborne and coastal oil spill monitoring applications.

A numerical study of damage evolution and crack propagation in backfill bodies of high-temperature thermal energy storage cavities in mines - Rui Zhan; Bo Zhang; Lang Liu; Chao Huan; Huisheng Qu; Huicong Xu; Jin Zhang; Hongjun Xi (Tunnelling and Underground Space Technology, 2026)

Bioactive edestin peptides from hemp (Cannabis sativa L.) seeds improve exercise performance under hypobaric hypoxia - Rui Zhang; Jie Liu; Liang-Liang Chen; Jia-Qi Liu; Xiao-Qian Jin; Zi-Xian Fu; Jun-Bin Xiong; Bin Jia; Jun-Ling Shi; Da-Chuan Yin (Food Research International, 2026)

Decoding the flavor formation mechanism of the functional microbial community in koji-mediated fish sauce - Jin-Xiu Xu; Xin Zhang; Bai-Feng Fu; Zhao-Rui Li; Min-Bo Li; Zhen-Yu Wang; Xian-Bing Xu; Shu-Zhen Cheng; Ming Du (Food Bioscience, 2026)

Data-driven discovery of high-performance surface passivators for efficient and stable perovskite solar cells - Feiyi Zhou; Zeyu Wang; Shangshang Zhao; Xu Zhang; Qingyue Guo; Runze Dai; Fanxiang Meng; Huajie Lyu; Jun Wan; Yi Dong; Zhe Jin; Shanqing Yu; et al. (Chemical Engineering Journal, 2026)

High-efficiency lithium extraction from brine using molybdenum-doped lithium manganate in hybrid capacitive deionization - Qingqing Han; Jiahui Zhang; Zixiang Liao; Junhao Zhu; Youfang Zhang; Lei Wu; Rui Wang; Huanwen Wang; Yansheng Gong; Jun Jin (Chemical Engineering Journal, 2026)

A combination of QTL mapping and genome‑wide association study revealed key genes for heat tolerance in maize - Xining Jin; Hangdan Qu; Pingxi Wang; Huaisheng Zhang; Tiantian Li; Xiangyuan Wu; Shilin Chen; Yaqiu Zhao; Fei Wang; Rui Song; Zhiyuan Fu; Xiaoxiang Zhang (Theoretical and Applied Genetics, 2026)

Trajectories of vegetation dynamics and their driving factors across China Ecosystem Research Network: A long-term assessment (2000–2024) - Shuyi Zhang; Ziwen Jin; Mengyao Ci; Ke Zeng; Yue Wang; Hanxin Tang; Rui Zhang; Chaolin Cai; Xianzhong Cao; Min Liu (Journal of Geographical Sciences, 2026)

Cloning, heterologous expression, and characterization of a metagenome-derived GH10 xylanase with salt and alkali tolerance from Xinjiang saline-alkali soil - Jing Gao; Hua-Lin Li; Mao-Song Li; Zong-Jin Shao; Zheng-Feng Yang; Chan-Jin Li; Zhi-Xin Zhang; Dan Zhu; Zhi-Hua Lv; Rong-Huan Song; Jian-Ling Li; Wei Hu; et al. (Antonie van Leeuwenhoek, 2026)

Responses of ecological stability in subtropical coastal phytoplankton communities to varying N:P ratios under present and future scenarios - Jichen Chen; Yonglong Xiong; Jingke Ge; Xin Zhao; Yuan Feng; Xu Li; Chi Song; Xiao Yang; Rui Zhang; Jin-Yu Terence Yang; Wuchang Zhang; Shengyao Sun; et al. (Water Research, 2026)

Quantitative study on the cave environmental factors for the fractionation of stable oxygen isotopes during the deposition of speleothem - Yue Jin; Chun-Jie Wang; Jian Zhang; Wen-Jun Sun; Chao-Jun Chen; Yao Wu; Hua-Yan Li; Yue-Hua Xiang; Yue-Yuan Lin; Xin-Rui Ye; Xin-Yan Li; Zhong-Lin Deng; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Geochemistry of tourmaline in granitic rocks from the Zharigana and Caolong areas, Northern Tibet: Implications for the identification of lithium-mineralizing plutons - Ling Ma; Jin-Sheng Zhou; Qiang Wang; Lin Ma; Jin-Heng Liu; Wu-Fu Li; Bing-Zhang Wang; Chun-Tao Wang; Jian-Dong Liu; Xin-Yuan Zhang; Mao-Rui Liu; Zhi-Wei Yu; et al. (Lithos, 2026)

Insight into the enhancement effect of pristine and amino-functionalized MWCNTs@SiO2 on the CO2 absorption and solar-driven regeneration performance of alkaline deep eutectic solvent based nanofluid system - Wei Wang; Yang Tang; Yi-Ming Chen; Rui-Rui Zhou; Zhang-Mao Hu; Jin-Cheng Huang (Journal of Environmental Chemical Engineering, 2026)

Hidden acidification beneath soil-covered mine waste dumps: links to oxygen-limited sulfur oxidation - Ziyi Li; Zhengbo Yue; Junyi Gu; Shu Wang; Lu Zhang; Zijie Yu; Rui Deng; Jin Wang (Journal of Environmental Management, 2026)

Improved corrosion resistance of amorphous-containing dual-structured micro-arc oxidation coatings on (Zr0.5Ti0.35Nb0.15)90Al10 high-entropy alloy - Luqi Chai; Xuehui Yan; Yubo Ma; Lijiao Wang; Xin Li; Chungang Guo; Chi Xu; Jiancheng Du; Xiaoyue Jin; Wenbin Xue; Menglu Zhang; Rui Zuo (Chemical Engineering Journal, 2026)

A room-temperature wireless NO2 gas sensor enabled by WO3 modified V2CTx nanosheets - Haineng Bai; Rui Guo; Yixin Zhou; Cheng Feng; Yiru Chen; Shengjie Zhang; Yamin Feng; Weifeng Liu; Kuili Liu; Fuqiang Guo; Jin Wang; Dunjun Chen; et al. (Chemical Engineering Journal, 2026)

Synergistic in-situ structural modification and interfacial engineering of lignin toward multifunctional biodegradable films - Rui Gao; Zekai Jin; Lidong Li; Chenhuan Lai; Xueni Sun; Fuxiang Chu; Yupeng Liu; Shishuai Gao; Daihui Zhang (Bioresource Technology, 2026)

Integrative Analysis the Role of ENG as a Metabolic and Macrophage-Related Gene in Hepatocellular Carcinoma - Songsong Fan; Yuhong Tang; Jun Cao; Rui Peng; Bingbing Su; Daoyuan Tu; Weidi Yu; Chen Chen; Shunyi Wang; Shengjie Jin; Guoqing Jiang; Chi Zhang; et al. (Biochemical Genetics, 2026)

Correction to: Urban perception analysis: integrating street view imageswith eye-tracking data - Jing Jin; Huifu Li; Rui Zhou; Su Li; Abdureyim Raxidin; Xun Zhang (Environment, Development and Sustainability, 2026)

Raccoon dog parvovirus NS1 protein antagonizes type I interferon signaling by promoting selective autophagic degradation of IRF3 - Wen-yu Cao; Rui-qi Wang; Jin-yang Zheng; Ping Ma; Bo Hu; Cheng-qi Zhang; Ya-jie Sun; Jia-jia Liu; Ding-rui Guo; Zi-han Zhao; Xin Cao; Xue Bai; et al. (Veterinary Microbiology, 2026)

Editor's note to “Source identification and component characterization of dissolved organic matter in an acid mine drainage reservoir” [Sci. Total Environ. 739 (2020), 139732] - Jin Wang; Siyu Zhang; Chen He; Xin Pan; Yunyun Li; Rui Shao; Quan Shi; Zhengbo Yue (Science of The Total Environment, 2026)

Heavy metal removal and concurrent stabilization of pig manure via constructed wetland-microbial fuel cell driven by sponge iron: Microbial response and mechanistic insight - Qingyun Zhang; Wanqing Jin; Xiaolu Tang; Xiang Mao; Rui Zuo; Yajun Hong; Dayong Xu (Process Safety and Environmental Protection, 2026)

Recent advances in cerium oxide redox cycle for solar thermochemical hydrogen production - Zilong Feng; Zeai Huang; Ruiyang Zhang; Shan Yu; Gang Feng; Decai Zhou; Guichuan Liu; Jiayi Liu; Ye Zhang; Jin Zhu; Jiarong Zhang; Yong He; et al. (Fuel, 2026)

Gliadin hydrolysate-chitosan bilayer nanoparticles for berberine delivery: Controlled release, enhanced antioxidant activity, and lipid digestion regulation - Xiaoxiao Li; Yi Zhao; Aimei Liao; Yinchen Hou; Xinrui Zhang; Hailong Tian; Luyang Wang; Jin Liu; Jinyang Zhang; Jihong Huang; Rui Tan (Food Chemistry, 2026)

Environmental stress and symbiotic shifts: The impact of perfluorooctanoic acid (PFOA) on soil microbe-plant networks - Zhan Chen; Jiajie Lou; Mengyao Yan; Rui Cui; Yicheng Jin; Mengwei Zhang; Rongshe Zhang; Shuduan Mao; Jun Chen; Liwei Sun; Tao Lu; Haifeng Qian (Environmental Pollution, 2026)

Glaucine suppresses IL-16/CD4 to alleviate neuropathic pain via spinal p56lck-NMDA receptor signaling - Xue Li; Rui Wang; Xiaonan Ma; Jin Yang; Shen Zhang; Zimeng Zhang; Han Jiang; Jihua Liu; Boyang Yu; Wenling Dai (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Multiplex PCR and nanopore sequencing reveal the genetic stability of Hantaan virus in Xi’an, China - Hailong Chen; Peng Zhang; Xiaoyue Chu; Yangni Deng; Mengying Yu; Leile Zhang; Quanli Du; Yuewen Han; Yujie Yang; Zerun Xue; Shuling Li; Rui Wu; et al. (Archives of Virology, 2026)

Correction to: Unveiling Differences in Source Apportionment and Optical Properties of Wintertime Carbonaceous Aerosols in Northern and Southern Chinese Cities - Rui Li; Qiyuan Wang; Jie Tian; Yong Zhang; TingTing Wu; Lu Qi; Yang Chen; Shaofei Kong; Suixin Liu; Jin Wang; Julian Shi; Yuemei Han; et al. (Aerosol Science and Engineering, 2026)

Urban perception analysis: integrating street view images with eye-tracking data - Jing Jin; Huifu Li; Rui Zhou; Su Li; Abdureyim Raxidin; Xun Zhang (Environment, Development and Sustainability, 2026)

Zinc finger protein ZNF638 in brown fat deteriorates type 1 diabetes via retinol binding protein 4 - Meiyao Meng; Shuang Liu; Yinzhao Zhong; Jingyi Hu; Lijun Zhu; Jin Qiu; Rui Wang; Yuan Luo; Yingwen Wang; Wenhao Zhou; Guangyu Shan; Zhenyu Du; et al. (Science Bulletin, 2026)

Ginkgonins A and B: Two new sesquiterpenoids from Streptomyces ginkgonis TH01 - Yun-Fei He; Jing Miao; Chao Jian; Rui-Jun Wang; Yong-Sheng Gao; Jie-Hao Jin; Xiao-Yi Chen; Ji-Dong Wang; Shao-Yong Zhang (Phytochemistry Letters, 2026)

Towards sustainable desertification control: A manufacturing method for porosity-controlled upright reed sand fences - Manyu Jin; Yijiang Zheng; Yun Ge; Baojian Ma; Jiangyu Zhang; Rui An; Jianjun Cheng (Journal of Environmental Management, 2026)

Aggregation kinetics and stability of Ce(IV)-borate colloid: Effect of pH, electrolytes, gibbsite colloid, and humic acid colloid - Kang Chen; Rui Zhang; Chunsheng Shi; Shanrong Yuan; Zishuo Li; Daming Zhang; Qiang Jin; Zhijun Guo; Zongyuan Chen (Journal of Contaminant Hydrology, 2026)

Evolution of soil arching under different initial water-saturation conditions via coupled SPH-DEM method - Rui-Xiao Zhang; Dong Su; Xiang-Sheng Chen; Xiu-Song Shi; De-Jin Zhang (Computers and Geotechnics, 2026)

Quantifying glacier and snow shrinkage: future water stress in Northern Tien Shan, Central Asia - Qiudong Zhao; Yongjian Ding; Zizhen Jin; Yan Qin; Rui He; Donghui Shangguan; Shiqiang Zhang; Yaping Chang; Haidong Han (CATENA, 2026)

A critical review of inhibitory effects of substrates and organic matter on anammox: mechanisms and mitigation strategies - Rui Zhao; Da Jin; Xiaonong Zhang; Luomiao Ji; Xurui Zhu; Bo Gao; Peng Wu (ENGINEERING Environment, 2026)

Scale-Dependent environmental influences on urban green space sentiment: Integrating multimodal social media analysis and explainable spatial models - Jiaqi Zhang; Jin Rui; Chenfan Cai (Journal of Environmental Management, 2026)

Sunlight-driven evolution of the aroma profile in fish sauce fermentation - Jin-Xiu Xu; Xin Zhang; Bai-Feng Fu; Zhao-Rui Li; Min-Bo Li; Zhen-Yu Wang; Xian-Bing Xu; Shu-Zhen Cheng; Ming Du (Food Bioscience, 2026)

TensorSymmetry: a package to get symmetry-adapted tensors disentangling spin-orbit coupling effect and establishing analytical relationship with magnetic order - Rui-Chun Xiao; Yuanjun Jin; Zhi-Fan Zhang; Zi-Hao Feng; Ding-Fu Shao; Mingliang Tian (Computer Physics Communications, 2026)

Activation of the Tp53 apoptosis signaling pathway by chelidonine induces cardiac developmental abnormalities in zebrafish larvae - Jin Gu; Yanwen Zheng; Jian Su; Rui Li; Chiyu Zhang; Han Wang; Zhaomin Zhong (Chemico-Biological Interactions, 2026)

Reconstruction of high-precision gridded precipitation dataset in the alpine cold regions of the Qilian Mountains: An intelligent technological framework from downscaling to calibration - Renjun Wang; Xiang Qin; Yushuo Liu; Jianyu Zhao; Rui Zhang; Zizhen Jin; Yanzhao Li; Wentao Du; Jizu Chen; Weijun Sun (Atmospheric Research, 2026)

Warming and precipitation alter soil viral community structure and functional characteristics in dryland wheat fields on the Loess Plateau, China - Jin Kou; Feiyan Zheng; Jiaxuan Lei; Ting Wang; Heling Wang; Kai Zhang; Rui Tian; Xiaodong Lyu (Plant and Soil, 2026)

Brown Adipose Tissue Activation Alleviates Cerebral Ischemia–Reperfusion Injury by Increasing 14–3-3ζ Secretion from Circulating Extracellular Vesicles to Suppress P53 Activity - Hui Yue; Xiaohua Wang; Yue Liu; Yinglian Zhou; Yifei Wang; Xuemei Zhang; Shan Huang; Changsi Ai; Jin Fu; Rui Wang (Molecular Neurobiology, 2026)

Mechanisms of Action of FUNDC1 in Cerebral Ischemia-Reperfusion Injury - Xin-Yi Zou; Luo-Yang Cai; Jin Zhang; Ying Yuan; Jie Song; Zhao-Duan Hu; Rui Peng; Xiao-Feng Ruan; Xiao-Ming Zhang (Molecular Neurobiology, 2026)

Spatiotemporal evolution of urban–rural ozone disparities and the “pollution transfer” effect in rapidly urbanizing regions - Rui Zhang; Shuyi Zhang; Hanxin Tang; Ke Zeng; Yue Wang; Jiarui Zhang; Mengyao Ci; Ziwen Jin; Min Liu (Urban Climate, 2025)

Precise construction of Anderson-type polyoxometalate-based covalent organic frameworks for photocatalytic hydrogen peroxide production - Zhang-Di Liu; Zai-Xiang Zhang; Yang Yang; Rui Xing; Zi-Hao Wei; Hou-He Liu; Jiang-Bo Ming; Jin Zhu; De-Yin Wang (Journal of Water Process Engineering, 2025)

Impacts of arsenic exposure through drinking water on pigment disorders: A meta-analysis and a Bayesian benchmark concentration analysis - Rujin Wang; Xingrun Li; Yuanjie Wei; Tingxu Jin; Yuanhui Zhu; Ting Zhang; Rui Yan; Heran Li; Koichi Kato; Runa A; Qianlei Yang; Yan An (Journal of Trace Elements in Medicine and Biology, 2025)

Highly efficient, selective, and sustainable adsorption of Nd3+ ion by amino-phosphonic acid functionalized polyacrylonitrile fibers via surface synergistic coordination - Xiao-Wei Zhang; Shuang Wang; Feng Guo; Jin-Xiu Wu; Yan-Hong Hu; Ming-Guang Chen; Rui-Lin Ren (Journal of Environmental Chemical Engineering, 2025)

Orbitally paced sedimentary records from the Neogene continental shelf margin and its implications for global sea-level changes - Zhinan Zhang; Siding Jin; Bin Deng; Rui Xiong; Chao Ma (Journal of Asian Earth Sciences, 2025)

Local electron structure regulation inhibits Jahn-Teller effect of Ni/Fe/Mn-based oxide cathode toward wide-temperature sodium-ion batteries - Yuhang Zhang; Shihao Li; Rui Jin; Fangyan Liu; Yi Zhang; Huiru Wang; Ziyue Qiu; Zhian Zhang (Chemical Engineering Journal, 2025)

Upcycling PET waste into carbon quantum dots as flame retardant of PET for closed-loop recycling - Jianfei Wei; Guocong Ma; Yaoyao Tang; Jing Zhang; Gaoling Jin; Chaohui Ma; Linhan Bing; Zhiguo Zhu; Zhenfeng Dong; Puzhen He; Ruichen Zhou; Rui Wang; et al. (Chemical Engineering Journal, 2025)

Different Chemical Fertilization Levels Affect Arbuscular Mycorrhizal Fungal Communities in Rhizosphere Soils of Ratoon Sugarcane - Xiao-Juan Qin; Sheng Wang; Ying-Jie Nong; Yi-Hao Kang; Jin-Lian Zhang; Shi-Yuan Zeng; Ting-Su Chen; Yang-Rui Li (Sugar Tech, 2025)

Integrating network pharmacology, molecular docking, and bioinformatics to explore the mechanism of sparganii rhizoma in the treatment of laryngeal cancer - Meiling Zheng; Rui Zhang; Xinxing Yang; Feiyan Wang; Xiaodi Guo; Long Li; Jin Wang; Yajun Shi; Shan Miao; Wei Quan; Shanbo Ma; Xiaopeng Shi (Molecular Diversity, 2025)

Sample Size and Optimal Timing for Urine Collection Based on Diurnal Variability of Urinary Iodine/Creatinine Ratio in Pregnant Women - Qi Meng; Min Fu; Rui Yang; Fei Li; Junjing Li; Meina Ji; Qi Jin; Mengxin Liu; Hexi Zhang; Wenxing Guo; Wanqi Zhang (Biological Trace Element Research, 2025)

Unveiling Differences in Source Apportionment and Optical Properties of Wintertime Carbonaceous Aerosols in Northern and Southern Chinese Cities - Rui Li; Qiyuan Wang; Jie Tian; Yong Zhang; TingTing Wu; Lu Qi; Yang Chen; Shaofei Kong; Suixin Liu; Jin Wang; Julian Shi; Yuemei Han; et al. (Aerosol Science and Engineering, 2025)

A Modified Iodine Balance Study to Explore the Recommended Nutrient Intake of Iodine in Chinese Preschool Children Aged 3 to 6 Years - Rui Yang; Qi Jin; Dong An; Dongping Lv; Yidan Wei; Elizabeth N. Pearce; Junhong Yang; Dongmei Meng; Jiayi Zhang; Weiwei Gao; Wen Chen (Biological Trace Element Research, 2025)

Transcriptomic analysis of the mechanism of male reproductive injuries caused by the mixture of three phthalates in rats - Ling-Zi Xia; Jun-Zhe Yue; Li-Jun Wu; Qian-Ying Jin; Yi-Pei Yang; Jing-Yang Yu; Rui-Zhe Pan; Xin Zhang; Xiao-Ying Wu; Jiayin Zhu; Hai-Tao Gao (Toxicology and Applied Pharmacology, 2025)

Biofilm-engineered nitrite transfer channeling from comammox to anammox drives autotrophic nitrogen removal in low-strength municipal wastewater - Da Jin; Rui Zhao; Xiaonong Zhang; Xingxing Zhang; Peng Wu (Journal of Environmental Management, 2025)

The potential of anthraquinone-2-sulfonate (AQS) for “shell breaking” of iron-coated denitrification granular sludge - Xin-Rui Zhang; Zhi-Han Xi; Zi-Jun Yan; Xin-Tao Liu; Ying Wang; Run-Mei Li; Zi-Yue Li; Ke-Yu Wu; Ren-Cun Jin; Zai-Yong Zhang; Qian-Qian Zhang (Journal of Environmental Management, 2025)

Denitrifying anaerobic methane oxidation reduces greenhouse gas emissions in floodplain sediments of the largest freshwater lake in China under flash drought - Rui Su; Lingtong Zhu; Xiaowei He; Hongjie Zhang; Rui Huang; Jin Zeng; Dayong Zhao (Journal of Environmental Management, 2025)

Optimizing lithium extraction from brines using fluoride-doped lithium titanate in hybrid capacitive deionization - Jiahui Zhang; Wen Xi; Jianing Hu; Qingqing Han; Youfang Zhang; Shuo Huang; Rui Wang; Huanwen Wang; Yansheng Gong; Jun Jin (Desalination, 2025)

Wireless gas sensor based on monolayer Ti3C2Tx-modified GaN/CuO heterostructures for ultrafast and trace detection of NO2 gas - Haineng Bai; Cheng Feng; Rui Guo; Yiru Chen; Wenfeng Yuan; Yunxiao Du; Yamin Feng; Weifeng Liu; Kuili Liu; Fuqiang Guo; Jin Wang; Dunjun Chen; et al. (Chemical Engineering Journal, 2025)

Synergistic enhancement of agricultural waste biochar in Cr(III)/methylene blue co-pollutant systems: Structure regulation and co-adsorption mechanistic insights - Binqiao Ren; Xue Han; Yu Jin; Yuying Zhang; Xiaoxiao Song; Luyang Zhao; Rui Liu (Journal of Environmental Chemical Engineering, 2025)

Adaptive responses and molecular mechanisms of Lactiplantibacillus plantarum to citric acid stress - Han Xie; Wei Zhang; Cong-Rong Shi; Rui-Shan Liu; Zhen-Ming Lu; Li-Juan Chai; Hong-Yu Xu; Jin-Song Shi; Xiao-Juan Zhang; Zheng-Hong Xu (International Journal of Food Microbiology, 2025)

Synthesis of confined palladium nanocatalysts in crystalline hemoglobin framework: An ultrastable nanoreactor for Cr(VI) detoxification - Xiao-Qian Jin; Jia-Lei Li; Jun-Bin Xiong; Rui Zhang; Chen-Yuan Li; Xue-Ting Wang; Wei-Hong Guo; Da-Chuan Yin (Environmental Research, 2025)

Sunlight-activated photochromic-photothermal nanofibrous textiles for self-monitored thermal management - Shuai Liang; An-Yang Duan; Shi-Kun Yan; Yan-Rui Zhao; Jin Zhang; Guo-Wei Xiao; Chang-Hai Xu; Ji-Xiang Hu; Guo-Ming Wang (Chemical Engineering Journal, 2025)

Halogen-sulfur synergy in benzodithiophene-benzodithienedione conjugated polymers: Molecular design of high-performance photoelectrodes for metal anti-corrosion - Rui Ding; Jin-ying Li; Yi-wen Zhang; Hao-han Cao; Xiao Liu; Yu-han Wang; Ming-di Lei; Yu-lin Zhang; An-lan Ji; Yu-chen Zhang; Jie Liu; Tai-jiang Gui; et al. (Chemical Engineering Journal, 2025)

Iron and Ferritin Dyshomeostasis Intersect with Sex, Age, and Disease Severity in Amyotrophic Lateral Sclerosis - Xiaoge Xie; Peng Wu; Ting Wen; Rui Jia; Ronghua Zhang; Fangfang Hu; Jiaoting Jin; Xing Qin; Qiao Yi Chen (Journal of Molecular Neuroscience, 2025)

Molecular and physiological insights into nicotine degradation by Pseudomonas alloputida Pa_12: Implications for environmental management and tobacco processing - Ang Li; Jie Zhang; Ao Li; Junaid Zafar; Ziling Wan; Yanqing Li; Rui Pang; Fengliang Jin; Xiaoxia Xu (Journal of Cleaner Production, 2025)

Reconstructing the tectonic evolution of the Mudanjiang Ocean: Metamorphic insights from the Heilongjiang Complex, NE China - Guang-Ming Sun; Xu-Ping Li; Hans-Peter Schertl; Jin-Rui Zhang; Xiao Wang; Wen-Yong Duan (Journal of Asian Earth Sciences, 2025)

Anion competitive coordination for solvation structure regulation in high-voltage sodium-ion batteries - Bowen Zhu; Jingkai Gao; Simin Li; Wei Zhou; Zhendong Yang; Rui Jin; Yi Zhang; Zixuan Ding; Yanqing Lai; Jie Li; Zhian Zhang (Chemical Engineering Journal, 2025)

Phylogenetic and toxicogenomic profiling of CYPomes to elucidate convergent and divergent insecticide resistance profiles in three rice planthopper species - Kai Lin; Hongxin Wu; Zhongsheng Li; Zichun Zhong; Liuyan He; Yujing Guo; Jie Zhang; Xiaoxia Xu; Wenqing Zhang; Fengliang Jin; Rui Pang (Journal of Pest Science, 2025)

Synergistic effects of PGPR and organic fertilizer on soil fertility, enzyme activities, and microbial community composition in saline-alkali rice systems - Mingfeng Guo; Junzhu Gao; Man Yang; Yawen Liu; Jiahui Fu; Rui Ma; Feng Xiong; Tingyu Zhang; Xuesheng Liu; Yu Jin; Juanjuan Qu (Applied Soil Ecology, 2025)

Xylem hydraulic impairment due to stronger drought stress accounts for the reduced crown vitality and growth performance of Mongolian pine trees in higher-density plantations - Xue-Wei Gong; Yi-Lei Ouyang; Yan-Yan Liu; Jin-En Zhang; Zhao-Kui Li; Hong-Li Li; Zhuo-Qun Fang; Yu Cao; De-Dong Wu; Qiu-Rui Ning; Guang-You Hao (Agricultural and Forest Meteorology, 2025)

Enhancing the anti-inflammatory efficacy of polysaccharides through processing techniques: a case study on Atractylodes macrocephala - Hong-Da Xuan; Sheng-Nan Shen; Chun-Jin Fu; Jie Zhou; Rui-Xing Chen; Jun-Zhe Zhang; Xiao-Xia Liu; Feng-Qin Li; Yi-Fan Zhao; Dong Zhang; Hai-Ning Lyu; Fang Wang (Natural Product Research, 2025)

Depletion of Albendazole and Its Metabolites and Their Impact on the Gut Microbial Community Following Multiple Oral Dosing in Yellow River Carp (Cyprinus carpio haematopterus) - Yue Liu; Yan Dai; Yan-Ni Zhang; Wen-Rui Wang; Yu-Xin Chen; Yang-Guang Jin; Long-Ji Sun; Shi-Hao Li; Fang Yang; Xing-Ping Li; Fan Yang (Fishes, 2025)
Healthy Yellow River carp (Cyprinus carpio haematopterus) reared at a water temperature of 23 ± 0.6 °C were orally administered albendazole (ABZ) at a dose of 12 mg/kg body weight (BW) once daily for seven consecutive days. At predetermined time points after the final administration, five fish were randomly selected for sampling. Plasma, skin-on-muscle, liver, and kidney tissues were collected, and the concentrations of ABZ and its three metabolites—albendazole sulfoxide (ABZSO), albendazole sulfone (ABZSO2), and albendazole-2-aminosulfone (ABZ-2-NH2−SO2)—were determined using high-performance liquid chromatography (HPLC). The results indicated that ABZ and ABZSO were widely distributed across tissues, while ABZSO2 and ABZ-2-NH2-SO2 were only present at trace levels. Pharmacokinetic analysis of ABZ and ABZSO in plasma and tissues was performed using noncompartmental analysis (NCA). ABZ peaked in plasma at 0.73 μg/mL at 24 h after the last administration, with an elimination half-life (t1/2λZ) of 38.56 h. ABZSO reached a peak plasma concentration of 1.54 μg/mL at 24 h, with a t1/2λZ of 53.73 h. According to China’s national standard, where ABZ-2-NH2−SO2 is the marker residue with a maximum residue limit (MRL) of 100 μg/kg in fish skin-on muscle, no withdrawal period was necessary. However, based on the European Union standard—which uses the sum of ABZ and its three metabolites as the marker residue and an MRL of 100 μg/kg in ruminants—a withdrawal period of 16 days (or 351 °C-days) was required. Additionally, the study assessed changes in the intestinal microbiota following multiple oral doses of ABZ. The results indicated that ABZ administration significantly altered microbial diversity and composition in a dose- and time-dependent manner. After drug withdrawal, the intestinal microbiota gradually returned to baseline levels, similar to the untreated control group.

Efficient and selective gold recovery from practical e-waste and electroplating wastewater using protein crystals - Xiao-Qian Jin; Jia-Lei Li; Chen-Yuan Li; Liang-Liang Chen; Xue-Ting Wang; Wen-Pu Shi; Jun-Bin Xiong; Rui Zhang; Wei-Hong Guo; Da-Chuan Yin (Resources, Conservation and Recycling, 2025)

Multi-target directed ligands design of 1-O-Acetylbritannilactone derivatives: Dual anti-neuroinflammatory and acetylcholinesterase inhibitory activities - Yan-Peng Liang; Qian Gao; Hong Chen; Rui Ma; Xiao-Bo Zhao; Xiao-Jie Jin; Jian Zhang; Yan-Ping Shi; Wei Ha (Phytochemistry Letters, 2025)

Predicting estrogen receptor agonists from plastic additives across various aquatic-related species using machine learning and AlphaFold2 - Wen-Jun Shi; Zhou Cao; Xiao-Bing Long; Chong-Rui Yao; Jin-Ge Zhang; Chang-Er Chen; Guang-Guo Ying (Journal of Hazardous Materials, 2025)

Sustainable remediation of butyl xanthate-contaminated mine wastewater by combining emergent macrophyte Cyperus alternifolius with a versatile bacterial isolate - Qi Liu; Yao-Yao Ye; Sha Yang; Cheng-Yu Cui; Huan Du; Jin-Cheng Ye; Ji-Liang Cheng; Rui-Wen Hu; Lei Xiang; Bai-Lin Liu; Yan-Wen Li; Quan-Ying Cai; et al. (Journal of Hazardous Materials, 2025)

Primary greisen-type tin mineralization: Insights from unidirectional solidification texture in oxidized, fluorine-rich ores from the Paleocene Kalonta Sn-W deposit, southern Myanmar - Jin-Xiang Li; Wei-Ming Fan; Rui Yuan; Lamu Ciren; Li-Yun Zhang; Fu-Long Cai; Ya-Hui Yue; Jing Xie; Lin Ding (Journal of Asian Earth Sciences, 2025)

Bioinspired trilayer poly(ε-caprolactone) scaffolds with native-like structures and mechanical property for heart valve constructs - Zeping Zhang; Rizheng Han; Yueen Liu; Xinqi Yu; Guixue Wang; Yun Bai; Rui Yang; Tao Jin; Xing Zhang (Chemical Engineering Journal, 2025)

Hydrogen-bonded organic framework-based signal amplification strategy combined with high-specificity sandwich immune response system for dual-mode ultrasensitive detection of gliadin allergen - Jie Han; Youfa Wang; Geoffrey I.N. Waterhouse; Yuxin Wang; Shuang Wu; Rui Wang; Xinxue Zhang; Yajie Tang; Vijaya Raghavan; Jin Wang (Chemical Engineering Journal, 2025)

The sequence of physiological stress thresholds responses to drought in a temperate mixed forest - Rui Zhang; Chuankuan Wang; Ruibing Duan; Lele Wang; Ying Jin (Agricultural and Forest Meteorology, 2025)

The prognostic significance of histopathological growth patterns in liver metastases undergoing surgery: a systematic review and meta-analysis - Xiang-Yu Wang; Bo Zhang; Yin-Chen Gu; Mei Yang; Bao-Rui Tao; Rong-Quan Sun; Yi-Tong Li; Zhen-Mei Chen; Sen-Feng Ying; Chen-He Yi; Yan Geng; Rui Zhang; et al. (Clinical & Experimental Metastasis, 2025)

Two new acorane-type sesquiterpenoids from an endophytic Trichoderma harzianum associated with Paeonia lactiflora Pall - Yun-Peng Sun; Man-Li Zhang; Yang Yu; Ran Sun; Si-Rui Wang; Jin-Song Liu; Guo-Kai Wang (Natural Product Research, 2025)

Sesquiterpenoids isolated from the root bark of Lycium chinense - Xiao-xia Wang; Qian Liu; Ning Wang; Rui-li Zhang; Xiao Li; Peng-yu Zhuang; Hang Liu; Liang-dan Sun; Yang Jin (Phytochemistry, 2025)

Chlorination treatment actuated structural reconstitution and aggravated toxicity of molybdenum disulfide nanosheets to freshwater algae - Qian Wang; Rui Li; Xingli Zhang; Tengfei Li; Caixia Jin; Wei Zou; Zhiguo Cao (Journal of Hazardous Materials, 2025)

Multidimensional analysis of sensory perception and neurophysiological responses to marinated beef cooked by diverse methods - Tianyi Yang; Wei Jiang; Chencheng Luo; Jin Hu; Wei Xu; Peng Zhang; Xiaofei Jin; Yuxuan Zhou; Rui Liu; Zhiyu Qian; Yamin Yang (Innovative Food Science & Emerging Technologies, 2025)

An integrated metabolomics-chemometrics strategy for discovering and characterizing potent anti-tyrosinase activity markers in functional tea Nelumbinis stamen - Yang Liu; Shujing Chen; Xue Meng; Jiake Wen; Rui Wang; Chengda Zhang; Kunze Du; Jin Li; Yanxu Chang (Food Bioscience, 2025)

Converting a D-/L lactic acid bacteria to its d-type counterpart via a combined chemical mutagenesis and biosensor screening method, and its application in lignocellulosic biorefinery - Xingwang Ma; Kang Yan; Yuwei Zhang; Xiaoyu Xie; Shujie Zou; Yuanyuan Sha; Rui Zhai; Zhaoxian Xu; Mingjie Jin (Bioresource Technology, 2025)

Responses of an invasive plant Alternanthera philoxeroides to cadmium, nutrient availability and water temperature - Zi-Yang Xie; Zhi-Hang Liu; Xin-Yue Gu; Yuan-Yuan Qin; Yu-Ting Du; Jin Yan; Rui Zhang; Chao Si (Aquatic Botany, 2025)

Enzyme- and nanozyme-based food allergen detections: from natural biocatalysts to rational engineering approaches - Shuang Wu; Jinlong Zhao; Youfa Wang; Vijaya Raghavan; Pengfei Dong; Xinxue Zhang; Jie Han; Rui Wang; Yajie Tang; Geoffrey I.N. Waterhouse; Jin Wang (Trends in Food Science & Technology, 2025)

Research on the dynamical behavior of air-dropped underwater profiler and virtual mooring strategy for variable pitch angle - Dingze Wu; Rui Zhou; Qingchao Xia; Puzhe Zhou; Xin Zhang; Zhilan Jin; Yang Zhang; Canjun Yang (Ocean Engineering, 2025)

Corrigendum to ‘Design of polypyrrole layer enhanced MIL-88B(Fe) composite electrode material for electrosorption separation of copper ions’ [Desalination 603 (15 May 2025) 118606] - Lujie Nie; Yanna Ren; Lei Wang; Yingying Wang; Jiajun An; Jiajin Hao; Jiaqi Wang; Chen Zhao; Xin Zhang; Yongtao Lv; Miaolu He; Hongyun Nie; et al. (Desalination, 2025)

Heavy-Duty Diesel Trucks on Highways in Beijing-Tianjin-Hebei: Constant Challenge in Pollution Control - Yingying Han; Chang Wang; Yixue Zhu; Rui Wu; Yifeng Xue; Xiang Zhang; Weiwei Wang; Yangyang Cui; Jinxiu Han; Zongbo Shi; Xiuyan Wang; Taosheng Jin (Water, Air, & Soil Pollution, 2025)

Development of a highly efficient seeding breeding system of Notopterygium incisum - Si Cheng Yao; Qiao Jia Peng; Na Su; Yuan Yuan Jiang; Jin Qiu Liao; Long Wang; Xue Xue Deng; Rui Wu Yang; Xiang Yun Chen; Li Zhang (Plant Biotechnology Reports, 2025)

Rational design and pairing of single-domain antibodies for developing rapid detection methods for botulinum neurotoxins A and B - Ruomei Lv; Jiaxin Li; Xinyu Fang; Li Tang; Rui Shi; Jin Wang; Wenjing Zhang; Jinglin Wang; Guangyu Zhao; Jing Wang; Shan Gao; Xuefang Xu; et al. (Analytica Chimica Acta, 2025)

Mass deposition of microbes from wildfire smoke to the sea surface microlayer - Siyao Yue; Yafang Cheng; Lishan Zheng; Senchao Lai; Shan Wang; Tianli Song; Linjie Li; Ping Li; Jialei Zhu; Meng Li; Lianfang Wei; Chaoqun Ma; et al. (Limnology and Oceanography, 2025)
Microbes in the sea surface microlayer (SML) are key to connecting the ocean and the atmosphere, affecting the exchange of matter, momentum, and heat at the interface. However, their sources have never been quantified systematically. Seawater has long been deemed their major source, whereas atmospheric deposition is regarded as trivial or merely providing additional nutrients. Here, combining atmospheric observations and quantitative budget analyses, we show that during the Indonesian peatland wildfire events the smoke can directly deposit abundant microbes into the SML, which can be comparable to the estimated supply from seawater and potentially diversify the microbial community of the SML. This land–air–ocean interaction is relevant for global climate, as it may induce previously unknown effects on the air–sea interactions, especially in an increasingly warming future with more intensifying wildfires.

Cascading environmental, phenological, and physiological influences on spatial variability of annual gross primary productivity in the Northern Hemisphere - Lang Han; Gui-Rui Yu; Zhi Chen; Qiu-Feng Wang; Xian-Jin Zhu; Wei-Kang Zhang; Tie-Jun Wang; Zhi-Feng Yan; Tian-You Zhang; Shi-Ping Chen; Hui-Min Wang; Jun-Hua Yan; et al. (Science of The Total Environment, 2025)

Palynological and geochemical evidence for East Asian monsoon evolution from the northern South China Sea during the middle to late Eocene - Mengtian Gao; Li You; Gaowei Hu; Manuel Chevalier; Xiaohua Teng; Qi Feng; Yabing Chen; Feng Jin; Rui Yang; Jingyu Zhang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Fabrication of CMC-PVA-EGDE hydrogels for maintaining overall postharvest quality of small-size packaged straw mushroom - Rui Jin; Xin-Lin Li; Wei Jia; Wen Li; Lei Sun; Yan Yang; Jing-Song Zhang; Wen-Jing Sun; Feng-Jie Cui (Food Chemistry, 2025)

Design of polypyrrole layer enhanced MIL-88B(Fe) composite electrode material for electrosorption separation of copper ions - Lujie Nie; Yanna Ren; Lei Wang; Yingying Wang; Jiajun An; Jiajin Hao; Jiaqi Wang; Chen Zhao; Xin Zhang; Yongtao Lv; Miaolu He; Hongyun Nie; et al. (Desalination, 2025)

Eccentricity and obliquity forcing of East Asian hydroclimate during the latest Cretaceous to early Paleocene - Xiaoyue Zhang; David B. Kemp; Ruiyao Zhang; Robert A. Spicer; Simin Jin; Rui Zhang; Ze Zhang; Chunju Huang (Earth and Planetary Science Letters, 2025)

Fabrication of flexible polymer-MOF composite electrolyte for solid-state lithium metal batteries with high rate performance - Jiansheng Gao; Yan Chai; Jialun Ni; Yong Zeng; Gaoyuan Zhang; Xueling Liu; De Ning; Xinghui Jin; Huajun Zhao; Dong Zhou; Rui Gao; Wei Wu; et al. (Chemical Engineering Journal, 2025)

Cation-induced phase transformation in PVDF for efficient energy harvesting - Dinku Hazarika; Jiaqi Lu; Jiafeng Ni; Chuanrui Chen; Muhammad Naeem Shah; Liangquan Xu; Jianhui Wu; Kaihang Zhang; Jie Li; Xinyu Cai; Rui Wan; Hao Jin; et al. (Chemical Engineering Journal, 2025)

Responses of plant biomass allocation to changed precipitation timing in a semi-arid steppe - Huiru Jin; Chunkun Fan; Hongyan Zhu; Yuxian Zhang; Rui Xiao; Zhongling Yang (Plant and Soil, 2025)

Fire increases the risk of hydraulic failure of woody species: Evidence from an experiment and a meta-analysis - Rui Zhang; Yaxin Zhang; Aolin Niu; Chuankuan Wang; Ying Jin (Agricultural and Forest Meteorology, 2025)

CORBES: Radiation belt survey with international small satellite constellation - Ji Wu; Li Deng; Jaan Praks; Marius Anger; Philipp Oleynik; Wojciech Hajdas; Jin-Dong Wang; Shen-Yi Zhang; Bin Zhou; Li Zeng; Jinbin Cao; David Fischer; et al. (Advances in Space Research, 2025)

Salinicoccus bachuensis sp. nov., a novel halophilic bacterium, isolated from rhizosphere soil surrounding Tamarix chinensis Lour. plants in Bachu County, Xinjiang, China - Zhen-Pu Liang; Rui Wang; Han-Wen Cao; Xin-Lu Zhou; Jin-Ping Dai; Ping Su; Deepali Singh; Xiao-Xia Zhang (Archives of Microbiology, 2025)

Dissimilatory nitrate reduction pathways drive high nitrous oxide emissions and nitrogen retention under the flash drought in the largest freshwater lake in China - Rui Su; Dayong Zhao; Xiaomin Zhang; Hongjie Zhang; Junxiang Cheng; Ligang Xu; Qinglong L. Wu; Jin Zeng (Water Research, 2025)

From city to countryside: Unraveling the long-term complex effects of urbanization on vegetation growth in China - Shuyi Zhang; Hongkai Zhu; Ke Zeng; Yiwen Zhang; Ziwen Jin; Yue Wang; Rui Zhang; Breuste Jürgen; Min Liu (Journal of Environmental Management, 2025)

Synthesis, characterization, and catalytic performance of a novel and efficient iron-based catalyst NaFeS2 for direct coal liquefaction - Rui Zhang; Bowen Tang; Haiyun Liu; Xin Zheng; Zhixian Bao; Lijun Jin; Jianli Wang; Haoquan Hu (Fuel, 2025)

Lactic acid bacteria-mediated transformation of black tea extract: Insights into metabolite profile and sensory characteristics - Zhi-Peng Cheng; Yao-Zeng Zhang; Zhong-Zheng Guan; Rui-shan Liu; Zhen-Ming Lu; Li-Juan Chai; Hong-Yu Xu; Jin-Song Shi; Xiao-Juan Zhang; Zheng-Hong Xu (Food Bioscience, 2025)

Dynamic characterization of the changes in intestinal fungi and fecal metabolites during the reproductive cycle of sows - Jin-Wen Su; Xin-Wen Hou; Shuo Liu; Yu Chen; Ji-Xin Zhao; Xiao-Xuan Zhang; Hong-Bo Ni; He Ma; Rui Liu (Veterinary Research Communications, 2025)

Molecular disruptions in microalgae caused by Acidithiobacillus ferrooxidans: Photosynthesis, oxidative stress, and energy metabolism in acid mine drainage - Meichen Wang; Zhengbo Yue; Rui Deng; Zhixiang She; Lu Zhang; Fan Yang; Jin Wang (Water Research, 2025)

Insight of oil-soluble Fe-based catalyst for direct liquefaction of Shangwan coal - Zhi Li; Yuxin Wen; Rui Zhang; Mei Zhong; Haiyun Liu; Xin Zheng; Haoquan Hu; Lijun Jin (Fuel, 2025)

Bacterial cellulose-based scaffold modified with anti-CD29 antibody to selectively capture urine-derived stem cells for bladder repair - Tianyi Shao; Mingzhe Yan; Rui Liu; Yanming Zhang; Banghui Wang; Yifei Li; Yuxin Liu; Danxia Li; Lixin Jin; Bingcheng Yi; Qihui Zhou (Carbohydrate Polymers, 2025)

Revealing disparities and driving factors in leisure activity segregation of residents and tourists: A data-driven analysis of smart phone data - Xun Zhang; Jin Rui; Geyang Xia; Junyan Yang; Chenfan Cai; Wenjia Zhao (Applied Geography, 2025)

Insights into the photoaging behavior of biodegradable and nondegradable microplastics: Spectroscopic and molecular characteristics of dissolved organic matter release - Xiaoyang Wu; Yifan Liu; Yaofeng Jin; Yue Wang; Mengjie Yuan; Kunyu He; Xiaoyan Zhang; Qin Chen; Zhijing Xue; Rui Wang; Xiaoyun Li (Journal of Hazardous Materials, 2025)

Anammox sludge granulation and synergy with comammox: A critical review - Rui Zhao; Xiaonong Zhang; Da Jin; Xurui Zhu; Luomiao Ji; Bo Gao; Peng Wu (Journal of Environmental Chemical Engineering, 2025)

Construction of low-toxicity cadmium sulfide/nitrogen-doped muti-walled carbon nanotubes for peroxymonosulfate activation: The crucial role of electron transfer - Jin Qian; Sai Bai; Mengqi Geng; Dandan Zhang; Guoping Xiang; Yichu Zhang; Yangju Li; Dongdong Chu; Di Wu; Rui Ma; Yueping Bao; Xiangning Xu; et al. (Environmental Research, 2025)

Ultrafast and ultrastable Na-ion storage in interface engineered MoS2/MXene nanohybrids with nanoconfinement for high-performance sodium-ion capacitors - Yuanhua Xiao; Qingling Le; Yang Kong; Wendi Lv; Dangcheng Su; Xianhong Rui; Shuyan Yu; Aiqing Zhang; Junhong Zhao; Qingxiang Yang; Qingxian Jin; Yujie Zheng; et al. (Chemical Engineering Journal, 2025)

Revealing the combined effect of hydroxylamine and hydrazine on nitrogen removal performance of completely autotrophic nitrogen removal over nitrite (CANON) process - Xin Ma; Jia-Min Zhou; Ying-Jun Sun; Xin-Tao Liu; Xin-Rui Zhang; Ying Wang; Ying Chen; Ren-Cun Jin; Qian-Qian Zhang (Bioresource Technology, 2025)

Nicotinamide riboside restores nicotinamide adenine dinucleotide levels and alleviates brain injury by inhibiting oxidative stress and neuroinflammation in a mouse model of intracerebral hemorrhage - Jing She; Hua Zhang; Hui Xu; Yan-Yan Li; Jun-Chao Wu; Rong Han; Fang Lin; Yan Wang; Rui Sheng; Jin-hua Gu; Zheng-Hong Qin (Molecular Neurobiology, 2025)
Hemorrhagic stroke is a global health problem owing to its high morbidity and mortality rates. Nicotinamide riboside is an important precursor of nicotinamide adenine dinucleotide characterized by a high bioavailability, safety profile, and robust effects on many cellular signaling processes. This study aimed to investigate the protective effects of nicotinamide riboside against collagenase-induced hemorrhagic stroke and its underlying mechanisms of action. An intracerebral hemorrhage model was constructed by stereotactically injecting collagenase into the right striatum of adult male Institute for Cancer Research mice. After 30 minutes, nicotinamide riboside was administered via the tail vein. The mice were sacrificed at different time points for assessments. Nicotinamide riboside reduced collagenase-induced hemorrhagic area, significantly reduced cerebral water content and histopathological damage, promoted neurological function recovery, and suppressed reactive oxygen species production and neuroinflammation. Nicotinamide riboside exerts neuroprotective effects against collagenase-induced intracerebral hemorrhage by inhibiting neuroinflammation and oxidative stress.

An efficient, high-throughput enrichment system for the rapid detection of E. coli at low concentrations in water - Binghuan He; Fangzhou Zhang; Pengfei Gong; Rui Sun; Jianxin Cheng; Chenghui Jin; Bo Liu; Jianlong Zhao; Shilun Feng; Bei Li (Analytica Chimica Acta, 2025)

Microglia programmed cell death in neurodegenerative diseases and CNS injury - Ling Cai; Qiuyue Fan; Rui Pang; Chen Chen; Yueman Zhang; Haiyi Xie; Jingyi Huang; Yu Wang; Peiying Li; Dan Huang; Xia Jin; Yuxi Zhou; et al. (Apoptosis, 2025)

Spatiotemporal estimates and health risks of atmospheric trace metals across Hong Kong during 2016–2020 - Wenwen Sun; Shenghua Zhang; Dongmei Cai; Liqiang Wang; Ji Jin; Rui Li; Zhenghu Chen (Air Quality, Atmosphere & Health, 2025)

Synergistic impacts of carbon emission trading policy and innovative city pilot policy on urban land green use efficiency in China - Rui Zhang; Lanjiao Wen; Yan Jin; Anlu Zhang; José M. Gil (Sustainable Cities and Society, 2025)

Bioconversion of agriculture by-products with functionally enhanced Streptomyces sp. SCUT-3: Fish skin as a model - Jing-Tao Ni; Ming-Shu Zhang; De-lin Lu; Wen-jun Lu; Lei Wu; Zhen-dong Yang; Can Qin; Zhen-jie Dai; Zhi-wei Li; Wen-jing Feng; Hua-hong Cai; Jia-rui Zhang; et al. (Food Chemistry, 2025)

A multirisk-rescued biomimetic nanozyme against periodontitis via inflammation targeting and microenvironment reprogramming - Lin Li; Rui-Xin Wu; Jia Wang; Rui Jin; Xin-Yu Zhang; Mei Xu; Si-Yao Li; Rui Gao; Bei-Min Tian; Xiao-Tao He; Fa-Ming Chen; Yuan Yin (Chemical Engineering Journal, 2025)

A flexible, highly sensitive, and anti-strain interference sensing fabric based on conjugated electrospinning core–shell conductive nanofiber yarns for ultra-stable pressure sensing and human–machine interaction - Wenqi Wu; Xu Jin; Adilaimu Tiliman; Fan Zhang; Ge Bai; Yurui He; Gaoling Jin; Bin Wang; Xiuqin Zhang; Rui Wang (Chemical Engineering Journal, 2025)

ZnCur nanoparticle-enhanced multifunctional hydrogel platform: Synergistic antibacterial and immunoregulatory effects for infected diabetic wound healing - Yan-Wen Ding; Zhi-Wei Zhang; Xin-Yu Cui; Rui-Yang Hu; Yang Li; Si-Da Huang; Si-Qi Du; Jin-Wei Dao; Dai-Xu Wei (Chemical Engineering Journal, 2025)

Genes involved in carbon, nitrogen, and sulfur cycling in an important estuarine ecosystem show coherent shifts in response to changes in environmental conditions - Sarah Pacocha Preheim; Shaina Morris; Yue Zhang; Chris Holder; Keith Arora‐Williams; Paul Gensbigler; Amanda Hinton; Rui Jin; Marie‐Aude Pradal; Morgan Buchanan; Anand Gnanadesikan (Limnology and Oceanography, 2025)
While metagenomics can provide insight into microbial community metabolic potential, understanding factors that influence gene abundance is necessary to maximize the information gained from this analysis. Gene abundances are influenced by chemical or physical conditions along with other factors, such as copy number variation between taxa, methodological biases, or issues associated with identification and classification. Here, we identify major drivers of spatiotemporal shifts in microbial gene relative abundance from multiple months, sites, and depths within Chesapeake Bay in 2017 using shotgun metagenomics. We compared changes in relative abundance of key genes for bacterial photosynthesis, nitrogen, and sulfur metabolism with each other and measured environmental variables. Major drivers of differences in key metabolic gene abundances are associated with environmental variables that largely change with depth and season (e.g., temperature, oxygen, phosphate). For sulfur oxidation, bacterial photosynthesis, and denitrification, genes within each process are generally significantly correlated with each other and with several environmental variables. For other processes, such as nitrification, nitrogen fixation, and dissimilatory nitrate reduction to ammonium, genes that encode enzymes within the same pathway are not well correlated. The lack of correlation typically results from differences in identified taxa carrying these genes, suggesting modular pathway structure, methodological errors, or discrepancies in gene copy number between taxonomic groups. To be suitable indicators of biogeochemical processes for models, genes or pathways should be strongly correlated with environmental variables and specific to and inclusive of all taxa mediating the associated process.

Effective identification of debris-covered glaciers in Western China using multiple machine-learning algorithms - Rui He; Donghui Shangguan; Qiudong Zhao; Shiqiang Zhang; Zizhen Jin; Yan Qin; Yaping Chang (Science of The Total Environment, 2024)

Evaluating pulmonary toxicity of PFOS and its alternative OBS using spheroids of A549 cells - Chong-Rui Yao; Yu-Xia Jiang; Si-Ying Li; Zhi-Jie Lu; Xiao-Bing Long; Na Xin; Jin-Ge Zhang; Dong-Dong Ma; Guang-Guo Ying; Wen-Jun Shi (Science of The Total Environment, 2024)

A review of nanoscale MnOx-based materials: Catalytic and oxidative properties for pollutant degradation in multiple mediums - Zi-Chun Lu; Hai-Zhu Liu; Rui Zhang; Bin Li; Jin-Xing Zhou; Hai-Feng Su (Journal of Water Process Engineering, 2024)

Effects of tauroursodeoxycholate on arsenic-induced hepatic injury in mice: A comparative transcriptomic analysis - Xiujuan Zheng; Jianbin Cao; He Wang; Lele Liu; Baiming Jin; Hua Zhang; Mingqi Li; Shijing Nian; Haonan Li; Rui He; Ningning Wang; Xuying Li; et al. (Journal of Trace Elements in Medicine and Biology, 2024)

Effect of yeast (Saccharomyces cerevisiae) fermentation on conformational changes in pig liver proteins and their ability to bind to characteristic aldehydes - Jin Luo; Li Liang; Jingcheng Zhang; Yongzhao Bi; Rui Yang; Baoguo Sun; Yuyu Zhang (Food Chemistry, 2024)

Lactococcus lactis subsp. lactis LJL7m20 strongly inhibits growth of the Bacillus cereus group from sufu - Jialu Xian; Huifang Wang; Siying Diao; Nan Zhang; Sisi Lin; Rui Zhang; Zekun Jin; Zhaohui Zhou; Liling Lu; Sameh A. Korma; Li Li (Food Bioscience, 2024)

Bacterial community and antibiotic resistance genes assembly processes were shaped by different mechanisms in the deep-sea basins of the Western Pacific Ocean - Qianyi Jin; Jialin Tang; Lilan Zhang; Rui Yang; Bowen Hou; Qijun Gong; Dong Sun (Environmental Pollution, 2024)

Multiomics analysis reveal the impact of 17α-Ethinylestradiol on mortality in juvenile zebrafish - Xiao-Bing Long; Chong-Rui Yao; Si-Ying Li; Jin-Ge Zhang; Zhi-Jie Lu; Dong-Dong Ma; Yu-Xia Jiang; Guang-Guo Ying; Wen-Jun Shi (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

Crystal and micro-nano structure bidirectional regulation of iron oxalate for high-lithium storage and ultralong-cycling life via ultrasound assistance - Qing Zhao; Keyu Zhang; Geng Gao; Bo Jin; Guangping Zi; Rui Yan; Binbin Li; Bin Yang; Yaochun Yao (Chemical Engineering Journal, 2024)

Integrative experimental and computational analysis of the impact of KGM's polymerization degree on wheat starch's pasting and retrogradation characteristics - Yi Zhao; Juan Wang; Rui He; Yuanyuan Ren; Jin Fu; Yunjun Zeng; Kangyi Zhang; Geng Zhong (Carbohydrate Polymers, 2024)

Community of Arbuscular Mycorrhizal Fungi in the Rhizosphere Soils with Different Generations of Hybridized Progeny of Wild Erianthus arundinaceus and Sugarcane - Jin-Lian Zhang; Yi-Hao Kang; Juan Song; Huan-Ying Xu; Wei Zhang; Ying-Jie Nong; Qian Wang; Qin-Nan Wang; Ting-Su Chen; Yang-Rui Li (Sugar Tech, 2024)

Small intestine structural and functional responses to environmental heavy metal stress in tree sparrow Passer montanus nestlings - Fei Jin; Yue Shen; Zhaocun Lin; Yuquan Miao; Yu Liu; Rui Su; Wenya Zhang; Yingmei Zhang (Environmental Science and Pollution Research, 2024)

Short-term sedimentary evidence for increasing diatoms in Arctic fjords in a warming world - Fu-Tao Fang; Zhuo-Yi Zhu; Fred Wenger; Jian-Zhong Ge; Jin-Zhou Du; Bing Deng; Hong-Mei Ma; Rui-Feng Zhang; Yu Zhang (Science of The Total Environment, 2024)

Seasonal wet–dry transition and denitrifying communities contributed to nitrous oxide emissions in the water-level fluctuating zone of the largest freshwater lake in China - Rui Su; Dayong Zhao; Xiaomin Zhang; Zixu Guo; Junxiang Cheng; Zhongbo Yu; Ligang Xu; Qinglong L. Wu; Jin Zeng (Journal of Hydrology, 2024)

A pretreatment-free and eco-friendly rapid detection for mycotoxins in edible oils based on magnetic separation technique - Baoxia Ni; Jin Ye; Zhihong Xuan; Li Li; Rui Zhang; Hongmei Liu; Songxue Wang (Food Chemistry, 2024)

An adaptive bionic sensor: enhancing ankle joint tracking with high sensitivity and superior cushioning performance - Jianqiao Jin; Chen Zhang; Jianyuan Zhao; Minghan Yu; Ming Lei; Chun Jin; Rui Yin; Weiwei Zhao (Chemical Engineering Journal, 2024)

Zirconium based metal–organic frameworks with aggregation-induced electrochemiluminescence for sensitive analysis of aflatoxin B1 by signal dual-amplification strategy - Yuan Li; Xue Dong; Tingting Wu; Xiaoyue Zhang; Xiang Ren; Rui Feng; Yu Du; Jin Yong Lee; Xuejing Liu; Qin Wei (Chemical Engineering Journal, 2024)

Inflammatory microenvironment activation-targeted self-delivery nanomedicine for effective rheumatoid arthritis treatment - Xinrui Dong; Haibao Liu; Rui Sun; Shuwen Tan; Gaoyang Li; Xuerou Jin; Xiaoqin Zhang; Zhiyi Xiao; Dingxiang Li; Jun-Li Cao; Xiaoran Deng (Chemical Engineering Journal, 2024)

In-situ growth of Ni, Co-Prussian blue nanocubes on molten salt etched lamellar Ti3C2Tx/Ni for enhanced hybrid capacitive deionization - Wen Xi; Youfang Zhang; Jianing Hu; Zongchang Li; Rui Wang; Huanwen Wang; Yansheng Gong; Beibei He; Jun Jin (Chemical Engineering Journal, 2024)

Association Between Recurrence of High-grade Squamous Intraepithelial Lesions of the Uterine Cervix and p16, C-myc and PIK3CA Proteins—A Single-center Retrospective Study - Ya Li; Rui Zhang; Jin Zhang; Ying Gao; Yawen Bian; Wenpei Bai (Cell Biochemistry and Biophysics, 2024)

A critical review of comammox and synergistic nitrogen removal coupling anammox: Mechanisms and regulatory strategies - Da Jin; Xiaonong Zhang; Xingxing Zhang; Li Zhou; Zixuan Zhu; Ufoymungu Kisa Deogratias; Zhiqiang Wu; Kangyu Zhang; Xu Ji; Ting Ju; Xurui Zhu; Bo Gao; et al. (Science of The Total Environment, 2024)

The OsNAC41-RoLe1-OsAGAP module promotes root development and drought resistance in upland rice - Shichen Han; Yulong Wang; Yingxiu Li; Rui Zhu; Yunsong Gu; Jin Li; Haifeng Guo; Wei Ye; Hafiz Ghualm Nabi; Tao Yang; Yanming Wang; Pengli Liu; et al. (Molecular Plant, 2024)

Genesis of high-Al chromitites from Xiaosuihe peridotite (Central Jilin Province, NE China): Implication for initial subduction of the Paleo-Asian ocean - Bing-Qian Ding; Fu-Ping Pei; Jing-Yang Wei; Jin-Rui Zhang; Zi-Cheng Guan; Kai Song; Tian-Jiao Sang; Peng-Yi Li (Lithos, 2024)

Exploring Jiangshui-originated probiotic lactic acid bacteria as starter cultures: Functional properties and fermentation performances in pear juice - Du-xin Jin; Yu-xuan Jin; Wei Zhang; Wei Cao; Rui Liu; Man-gang Wu; Qing-feng Ge; Hai Yu (Food Bioscience, 2024)

Myo-inositol: A potential game-changer in preventing gill cell death and alleviating “gill rot” in grass carp (Ctenopharyngodon idellus) - Jie Chen; Wei-Dan Jiang; Lin Feng; Pei Wu; Yang Liu; Xiao-Wan Jin; Hong-Mei Ren; Jia-Yong Tang; Rui-Nan Zhang; Xiao-Qiu Zhou (Fish & Shellfish Immunology, 2024)

Reason and control strategy for denitrification and anammox sludge flotation in nitrogen removal process: Mechanisms, strategies and perspectives - Xin Ma; Xin-Rui Zhang; Ying-Jun Sun; Zhi-Han Xi; Jin-Ze Liu; Ze-Tong Feng; Jia-Min Zhou; Xin-Tao Liu; Ying Wang; Ren-Cun Jin; Qian-Qian Zhang (Environmental Research, 2024)

Study on the necessity of setting up the heat removal system in subway tunnels in cold regions - Huan Zhang; Rui Jin; Jiaxuan Pu; Wandong Zheng (Energy and Buildings, 2024)

Tracking the Molecular-Scale Mechanistic Pathway of Trapping-Bonding CTAB/Fe3O4-AS for High-Performance Cr(VI) Adsorption - Binqiao Ren; Yu Jin; Xiaoxiao Song; Luyang Zhao; Xue Han; Yuying Zhang; Chongwei Cui; Rui Liu; Han Cui (Chemical Engineering Journal, 2024)

QTL mapping and omics analysis to identify genes controlling kernel dehydration in maize - Xining Jin; Xiaoxiang Zhang; Pingxi Wang; Juan Liu; Huaisheng Zhang; Xiangyuan Wu; Rui Song; Zhiyuan Fu; Shilin Chen (Theoretical and Applied Genetics, 2024)

Encouraging cycling through the improvement of streetscape perception: A bottom-up investigation into the relationship between street greening and bicycling volume - Qiao Zhang; Jin Rui; Yufei Wu (Applied Geography, 2024)

Cuproptosis-Associated lncRNA Gene Signature Establishes New Prognostic Profile and Predicts Immunotherapy Response in Endometrial Carcinoma - Xi-Ya Jiang; Jing-Jing Hu; Rui Wang; Wei-Yu Zhang; Qin-Qin Jin; Yin-Ting Yang; Jie Mei; Lin Hong; Hui Yao; Feng Tao; Jie-Jie Li; Yu Liu; et al. (Biochemical Genetics, 2024)
Uterine corpus endometrial carcinoma (UCEC), a prevalent kind of cancerous tumor in female reproductive system that has a dismal prognosis in women worldwide. Given the very limited studies of cuproptosis-related lncRNAs (CRLs) in UCEC. Our purpose was to construct a prognostic profile based on CRLs and explore its assess prognostic value in UCEC victims and its correlation with the immunological microenvironment.Methods: 554 UCEC tumor samples and 23 normal samples’ RNA-seq statistics and clinical details were compiled from data in the TCGA database. CRLs were obtained using Pearson correlation analysis. Using LASSO Cox regression, multivariate Cox regression, and univariate Cox regression analysis, six CRLs are confirmed to develop a risk prediction model at last.We identified two main molecular subtypes and observed that multilayer CRLs modifications were related to patient clinicopathological features, prognosis, and tumor microenvironment (TME) cell infiltration characteristics, and then we verified the prognostic hallmark of UCEC and examined its immunological landscape.Finally, using qRT-PCR, model hub genes’ expression patterns were confirmed. Results: A unique CRL signature was established by the combination of six differently expressed CRLs that were highly linked with the prognosis of UCEC patients. According to their CRLs signatures, the patients were divided into two groups: the low-risk and the high-risk groups. Compared to individuals at high risk, patients at low risk had higher survival rates ( p

TNF-α and RPLP0 drive the apoptosis of endothelial cells and increase susceptibility to high-altitude pulmonary edema - Yi-Ling Ge; Pei-Jie Li; Ying-Rui Bu; Bin Zhang; Jin Xu; Si-Yuan He; Qing-Lin Cao; Yun-Gang Bai; Jin Ma; Lin Zhang; Jie Zhou; Man-Jiang Xie (Apoptosis, 2024)
High-altitude pulmonary edema (HAPE) is a fatal threat for sojourners who ascend rapidly without sufficient acclimatization. Acclimatized sojourners and adapted natives are both insensitive to HAPE but have different physiological traits and molecular bases. In this study, based on GSE52209, the gene expression profiles of HAPE patients were compared with those of acclimatized sojourners and adapted natives, with the common and divergent differentially expressed genes (DEGs) and their hub genes identified, respectively. Bioinformatic methodologies for functional enrichment analysis, immune infiltration, diagnostic model construction, competing endogenous RNA (ceRNA) analysis and drug prediction were performed to detect potential biological functions and molecular mechanisms. Next, an array of in vivo experiments in a HAPE rat model and in vitro experiments in HUVECs were conducted to verify the results of the bioinformatic analysis. The enriched pathways of DEGs and immune landscapes for HAPE were significantly different between sojourners and natives, and the common DEGs were enriched mainly in the pathways of development and immunity. Nomograms revealed that the upregulation of TNF-α and downregulation of RPLP0 exhibited high diagnostic efficiency for HAPE in both sojourners and natives, which was further validated in the HAPE rat model. The addition of TNF-α and RPLP0 knockdown activated apoptosis signaling in endothelial cells (ECs) and enhanced endothelial permeability. In conclusion, TNF-α and RPLP0 are shared biomarkers and molecular bases for HAPE susceptibility during the acclimatization/adaptation/maladaptation processes in sojourners and natives, inspiring new ideas for predicting and treating HAPE.

Inorganic Carbon Pools and Their Drivers in Grassland and Desert Soils - Longwei Dong; Jinzhi Ran; Jiali Luo; Lin Bai; Ying Sun; Muhammad Aqeel; Yahui Zhang; Xiaoting Wang; Qiajun Du; Junlan Xiong; Haiyang Gong; Qingqing Hou; et al. (Global Change Biology, 2024)
Inorganic carbon is an important component of soil carbon stocks, exerting a profound influence on climate change and ecosystem functioning. Drylands account for approximately 80% of the global soil inorganic carbon (SIC) pool within the top 200 cm. Despite its paramount importance, the components of SIC and their contributions to CO 2 fluxes have been largely overlooked, resulting in notable gaps in understanding its distribution, composition, and responses to environmental factors across ecosystems, especially in deserts and temperate grasslands. Utilizing a dataset of 6011 samples from 173 sites across 224 million hectares, the data revealed that deserts and grasslands in northwestern China contain 20 ± 2.5 and 5 ± 1.3 petagrams of SIC in the top 100 cm, representing 5.5 and 0.76 times the corresponding soil organic carbon stock, respectively. Pedogenic carbonates (PIC), formed by the dissolution and re‐precipitation of carbonates, dominated in grasslands, accounting for 60% of SIC with an area‐weighted density of 3.4 ± 0.4 kg C m −2 at 0–100 cm depth, while lithogenic carbonates (LIC), inherited from soil parent materials, prevailed in deserts, constituting 55% of SIC with an area‐weighted density of 7.1 ± 1.0 kg C m −2 . Soil parent materials and elevation determined the SIC stocks by regulating the formation and loss of LIC in deserts, whereas natural acidification, mainly induced by rhizosphere processes including cation uptake and H + release as well as precipitation, reduced SIC (mainly by PIC) in grasslands. Overall, the massive SIC pool underscores its irreplaceable role in maintaining the total carbon pool in drylands. This study sheds light on LIC and PIC and highlights the critical impact of natural acidification on SIC loss in grasslands.

Simultaneous removal of nitrate nitrogen and ammonium nitrogen by partial denitrification coupled with anammox synergy by zero-valent iron - Jia-Min Zhou; Ying-Jun Sun; Zhi-Han Xi; Zu-Gang Liao; Xin Ma; Ze-Tong Feng; Xin-Tao Liu; Xin-Rui Zhang; Ying Wang; Ying Chen; Ren-Cun Jin; Qian-Qian Zhang (Journal of Cleaner Production, 2024)

Assessing the preservation of orbital signals across different sedimentary environments: Insights from stochastic sedimentation modeling - Meng Wang; Mingsong Li; Elizabeth A. Hajek; David B. Kemp; Yujing Wu; Hanyu Zhu; Chunju Huang; Haotian Zhang; Kaixuan Ji; Rui Zhang; Ren Wei; Zhijun Jin (Earth and Planetary Science Letters, 2024)

Feasibility and safety of percutaneous intramyocardial septal cryoablation: A canine model with 6-month follow-up - Xiaonan Lu; Jing Li; David H. Hsi; Juan Zhang; Yupeng Han; Shengjun Ta; Jing Wang; Jin He; Jia Zhao; Chao Han; Lu Yao; Xumei Ou; et al. (Cryobiology, 2024)

Efficient photocatalytic degradation of 24 imidazolium ionic liquids in an N-ZnO/simulated sunlight irradiation system and its mechanism - Jiaoqin Liu; Jingjing Zhang; Mengye Jia; Rui Ma; Ruijuan Qu; Zunyao Wang; Zhaoguo Liu; Yu Jiang; Haoxiang Zhang; Yujia Bai; Riya Jin; Yina Qiao; et al. (Chemical Engineering Journal, 2024)

Constructing interfacial chemical interaction of dual-carbon protected cobalt diselenide anode for sodium storage - Xiaoying Liu; Dongdong Xue; Rui Ren; Ting Ou; Tao Sun; Yuchen Han; Fan Jin; Yannan Li; Yan Zhao; Jiangwei Zhang (Chemical Engineering Journal, 2024)

Solvent-vapor-triggered crystallization of a ZIF-90 membrane with versatile separation properties towards light hydrocarbons - Xu Wang; Rui Yao; Han Zhu; Zinan Zhang; Lifeng Zhang; Qiang Ma; Hua Jin; Yanshuo Li (Chemical Engineering Journal, 2024)

Outdoor tubular photobioreactor microalgae-microorganisms biofilm treatment of municipal wastewater: Enhanced heterotrophic assimilation and synergistic aerobic denitrogenation - Pan Li; Yajun Luo; Jiansong Tian; Yiwei Cheng; Shiji Wang; Xin An; Jingxian Zheng; Heng Yan; Hongtao Duan; Jin Zhang; Zhicheng Pan; Yangwu Chen; et al. (Bioresource Technology, 2024)

Mechanisms for carbon stock driving and scenario modeling in typical mountainous watersheds of northeastern China - Jin Zhang; Wen-Guang Zhang; Xin-Yan Zhang; Yu-Hong Li; Ming-Ming Feng; Peng Qi; Yi-Qiang Huang; Rui Li; Ming Jiang; Yuan-Chun Zou; Yi Wu (Environmental Monitoring and Assessment, 2024)

Correction to: Calcitriol Inhibits NaAsO2 Triggered Hepatic Stellate Cells Activation and Extracellular Matrix Oversecretion by Activating Nrf2 Signaling Pathway Through Vitamin D Receptor - Dapeng Wang; Rui He; Qian Song; Heng Diao; Ying Jin; Aihua Zhang (Biological Trace Element Research, 2024)

Exploring the neural correlates of fat taste perception and discrimination: Insights from electroencephalogram analysis - Tianyi Yang; Peng Zhang; Jin Hu; Wei Xu; Wei Jiang; Rui Feng; Yajun Lou; Xiaofei Jin; Zhiyu Qian; Fan Gao; Keqiang Gao; Rui Liu; et al. (Food Chemistry, 2024)

Active prelithiation strategies for advanced lithium storage systems: A perspective from electrochemical mechanism to structural design and application - Bo Jin; Keyu Zhang; Geng Gao; Qing Zhao; Xinyu Jiang; Dingfang Cui; Keqi Chen; Xiang Lin; Liuliu Liu; Rui Yan; Bin Yang; Yaochun Yao (Chemical Engineering Journal, 2024)

Controlling amine monomers via UiO-66-NH2 defect sites to enhance forward osmosis membrane performance for lithium recovery - Miaolu He; Weiting Zhang; Huihui Zhang; Jie Lian; Yunlong Gao; Jin Wang; Yongtao Lv; Xudong Wang; Rui Miao; Lei Wang (Chemical Engineering Journal, 2024)

A Permeability Prediction Model of Single-Peak NMR T2 Distribution in Tight Sandstones: A Case Study on the Huangliu Formation, Yinggehai Basin, China - Jing Zhao; Zhilong Huang; Jin Dong; Jingyuan Zhang; Rui Wang; Chonglin Ma; Guangjun Deng; Maguang Xu (Mathematical Geosciences, 2024)

Calcitriol Inhibits NaAsO2 Triggered Hepatic Stellate Cells Activation and Extracellular Matrix Oversecretion by Activating Nrf2 Signaling Pathway Through Vitamin D Receptor - Dapeng Wang; Rui He; Qian Song; Heng Diao; Ying Jin; Aihua Zhang (Biological Trace Element Research, 2024)

Detoxification and removal of heavy metal by an acid-tolerant microalgae, Graesiella sp. MA1 - Lu Zhang; Jin Wang; Rui Shao; Xin Chuai; Shaoping Wang; Zhengbo Yue (Journal of Water Process Engineering, 2024)

Hydrogen-donating behavior and hydrogen-shuttling mechanism of liquefaction solvents under Fe- and Ni-based catalysts - Haiyun Liu; Rui Zhang; Xin Zheng; Jing Xie; Bowen Tang; Zhi Li; Erguang Guo; Haoquan Hu; Lijun Jin (Fuel, 2024)

Electrochemiluminescence detection of diazinon in vegetables based on the synergistic interaction of WO3-x dots with Au@SiO2 nanocapsules - Wenzheng Liu; Haifang Wang; Peisen Li; Chengqiang Li; Donghan Li; Zhenying He; Yuhao Zhang; Jingcheng Huang; Jin Hua; Rui Xu; Lianming Xia; Yemin Guo; et al. (Food Chemistry, 2024)

Phyllanthus emblica Linn: A comprehensive review of botany, traditional uses, phytonutrients, health benefits, quality markers, and applications - Qin-Ge Ma; Lei Wang; Rong-Hua Liu; Jin-Bin Yuan; Hui Xiao; Zhang-Yang Shen; Jia-Xin Li; Jia-Zeng Guo; Lan Cao; Hui-Lian Huang; Rong-Rui Wei (Food Chemistry, 2024)

Reindeer (Rangifer tarandus) hindlimb joint kinetics: propulsive and energy storage mechanisms and mechanical work - Guoyu Li; Rui Zhang; Hao Pang; Junfeng Wang; Dan Jin; Xumin Sun; Dianlei Han; Zhisong Li; Lige Wen (Polar Biology, 2024)

Targeting cathepsin L in the regulation of apoptosis in peripheral T-cell lymphoma - Rui Zhang; Yanjie Ruan; Yiming Zhao; Fengbo Jin; Mingzhen Yang; Zhimin Zhai (Molecular & Cellular Toxicology, 2024)

Investigation of the Inhibitory Effects of Illicium verum Essential Oil Nanoemulsion on Fusarium proliferatum via Combined Transcriptomics and Metabolomics Analysis - Cui-Qiong Ling; Hong-Xin Liao; Jin-Rui Wen; Hong-Yan Nie; Li-Yan Zhang; Fu-Rong Xu; Yong-Xian Cheng; Xian Dong (Current Microbiology, 2024)

Whole exome sequencing analyses reveal novel genes in telomere length and their biomedical implications - Wei-Shi Liu; Bang-Sheng Wu; Liu Yang; Shi-Dong Chen; Ya-Ru Zhang; Yue-Ting Deng; Xin-Rui Wu; Xiao-Yu He; Jing Yang; Jian-Feng Feng; Wei Cheng; Yu-Ming Xu; et al. (GeroScience, 2024)

Organic-mineral colloids regulate the migration and fractionation of rare earth elements in groundwater systems impacted by ion-adsorption deposits mining in South China - Xiao-Rui Liu; Wen-Shen Liu; Miaoyue Zhang; Chao Jin; Keng-Bo Ding; Alan J.M. Baker; Rong-Liang Qiu; Ye-Tao Tang; Shi-Zhong Wang (Water Research, 2024)

A randomised double-blind placebo-controlled trial of a probiotic combination for manipulating the gut microbiota and managing metabolic syndrome - Rui Xiao; Ying Chen; Xiaofeng Zhu; Linlin Wang; Peijun Tian; Xing Jin; Ming Liang; Zehua Chen; Ting Zhang; Long Qian; Qun Wang; Jianxin Zhao; et al. (Food Bioscience, 2024)

Recent advances of 2D materials in capacitive deionization - Jun Jin; Wen Xi; Zongchang Li; Jianing Hu; Rui Wang; Yansheng Gong; Beibei He; Huanwen Wang; Youfang Zhang (Desalination, 2024)

Improved seed yield and phosphorus accumulation in soybean are associated with the enhanced root exudates in south-west China - Hong-Lan Zhang; Nian Liang; Rui Dong; Chang-An Liu; Chun-Ling Hao; Kadambot H. M. Siddique; Jin He (Plant and Soil, 2024)

Exogenous application of salicylic acid improves eradication of apple stem grooving virus and apple chlorotic leaf spot virus in apple - Xiao-Yan Ma; Jin-Wei Li; Qing Li; Zi-Han Yan; Xi Cheng; Min-Rui Wang; Zhibo Hamborg; Lu Bao; Dong Zhang; Min-Ji Li (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

Potential in exosome-based targeted nano-drugs and delivery vehicles for posterior ocular disease treatment: from barriers to therapeutic application - Xingru Peng; Tingting Zhang; Rui Liu; Xin Jin (Molecular and Cellular Biochemistry, 2024)

Early Cretaceous intrusive rocks in the Gangdese arc of southern Tibet do not support shallow subduction of the Neo-Tethyan oceanic lithosphere - Feng Wang; Qing Wang; Di-Cheng Zhu; Shi-Min Li; Peter A. Cawood; Rui-Qiang Wang; Jian-Kang Yi; Liang-Liang Zhang; Jin-Cheng Xie (Lithos, 2024)

Assessment and management for future habitat risks under the implementation of China's territorial spatial planning: A case study from Hainan Island - Xiaolin Zhang; Xiaobin Jin; Xinyuan Liang; Xu Shi; Rui Sun; Wenjie Zhu; Jinhuang Lin; Bo Han; Yinkang Zhou (Environmental Impact Assessment Review, 2024)

Circular RNA MKLN1 promotes epithelial-mesenchymal transition in pulmonary fibrosis by regulating the miR-26a/b-5p/CDK8 axis in human alveolar epithelial cells and mice models - Yong Zhu; Xiaoxiao Meng; Xian Zhu; Jiaxiang Zhang; Hui lv; Feiyao Wang; Jinfeng Wang; Cheng Chen; Mengting Chen; Dapeng Wang; Wei Jin; Rui Tian; et al. (Archives of Toxicology, 2024)
Pulmonary fibrosis involves destruction of the lung parenchyma and extracellular matrix deposition. Effective treatments for pulmonary fibrosis are lacking and its pathogenesis is still unclear. Studies have found that epithelial-mesenchymal transition (EMT) of alveolar epithelial cells (AECs) plays an important role in progression of pulmonary fibrosis. Thus, an in-depth exploration of its mechanism might identify new therapeutic targets. In this study, we revealed that a novel circular RNA, MKLN1 (circMKLN1), was significantly elevated in two pulmonary fibrosis models (intraperitoneally with PQ, 50 mg/kg for 7 days, and intratracheally with BLM, 5 mg/kg for 28 days). Additionally, circMKLN1 was positively correlated with the severity of pulmonary fibrosis. Inhibition of circMKLN1 expression significantly reduced collagen deposition and inhibited EMT in AECs. EMT was aggravated after circMKLN1 overexpression in AECs. MiR-26a-5p/miR-26b-5p (miR-26a/b), the targets of circMKLN1, were confirmed by luciferase reporter assays. CircMKLN1 inhibition elevated miR-26a/b expression. Significantly decreased expression of CDK8 (one of the miR-26a/b targets) was observed after inhibition of circMKLN1. EMT was exacerbated again, and CDK8 expression was significantly increased after circMKLN1 inhibition and cotransfection of miR-26a/b inhibitors in AECs. Our research indicated that circMKLN1 promoted CDK8 expression through sponge adsorption of miR-26a/b, which regulates EMT and pulmonary fibrosis. This study provides a theoretical basis for finding new targets or biomarkers in pulmonary fibrosis.

Considering product life cycle characteristics and industry background in environmental impact analysis and application: a case study of a television - Lei Zhang; Yu Zheng; Rui Jin; Shiwen Pan; Junkai Huang (Environmental Science and Pollution Research, 2024)

DeepWMH: A deep learning tool for accurate white matter hyperintensity segmentation without requiring manual annotations for training - Chenghao Liu; Zhizheng Zhuo; Liying Qu; Ying Jin; Tiantian Hua; Jun Xu; Guirong Tan; Yuna Li; Yunyun Duan; Tingting Wang; Zaiqiang Zhang; Yanling Zhang; et al. (Science Bulletin, 2024)

Screening androgen receptor agonists of fish species using machine learning and molecular model in NORMAN water-relevant list - Xiao-Bing Long; Chong-Rui Yao; Si-Ying Li; Jin-Ge Zhang; Zhi-Jie Lu; Dong-Dong Ma; Chang-Er Chen; Guang-Guo Ying; Wen-Jun Shi (Journal of Hazardous Materials, 2024)

Multifunctional packaging film with sustained release behavior triggered by pH microenvironment for efficient preservation of pork - Wenze Wang; Liang Zhang; Puyuan Hu; Yuxuan Wang; Xinyi Jin; Rui Chen; Wentao Zhang; Yongsheng Ni; Jianlong Wang (Food Chemistry, 2024)

Molten salt etching synthesis of Ti3C2Tx/Ni composites for highly efficient capacitive deionization - Wen Xi; Tianzhuo Guo; Zeren Xie; Youfang Zhang; Rui Wang; Yansheng Gong; Beibei He; Huanwen Wang; Jun Jin (Desalination, 2024)

Effect of Regional Brain Activity Following Repeat Transcranial Magnetic Stimulation in SCA3: A Secondary Analysis of a Randomized Clinical Trial - Xia Liu; Lin Zhang; Hao-Lin Xu; Xia-Hua Liu; Arif Sikandar; Meng-Cheng Li; Xiao-Yue Xia; Zi-Qiang Huang; Na-Ping Chen; Yu-Qing Tu; Jian-Ping Hu; Shi-Rui Gan; et al. (The Cerebellum, 2024)

TRIM5 as a promising diagnostic biomarker of hepatocellular carcinoma: integrated analysis and experimental validation - Huanxiang Liu; Yuhong Tang; Jiahao Zhang; Gefeng Wu; Qing Peng; Chen Chen; Jun Cao; Rui Peng; Bingbing Su; Daoyuan Tu; Guoqing Jiang; Qian Wang; et al. (Functional & Integrative Genomics, 2024)

Spatiotemporal evolution of population exposure to multi-scenario rainstorms in the Yangtze River Delta urban agglomeration - Yaru Zhang; Rui Yao; Zhizhou Zhu; Hengxu Jin; Shuliang Zhang (Journal of Geographical Sciences, 2024)

The Complete Genomic Sequence of Microbial Transglutaminase Producer, Streptomyces mobaraensis DSM40587 - Xi-long Feng; Rui-qi Zhang; Wei-ge Dong; Zhen-xin Wang; Jun-jie Xiao; Jing Wei; Jin-ming Gao; Jianzhao Qi (Biochemical Genetics, 2024)

An improved analytical model for rainfall infiltration in embankment slope constructed with red-bed solid waste - Jianqing Jiang; Shilin Luo; Jin Chang; Rui Zhang (Transportation Geotechnics, 2024)

Weak correlations among leaf thermal metrics, economic traits and damages under natural heatwaves - Qiu-Rui Ning; Qiang Li; Hao-Ping Zhang; Yi Jin; Xue-Wei Gong; Rui-Fang Jiao; Emily Patience Bakpa; Han Zhao; Hui Liu (Science of The Total Environment, 2024)

Nitrate leaching characteristics of red soils from different parent materials in subtropical China - Yue Dong; Jin-Ling Yang; Xiao-Rui Zhao; Shun-Hua Yang; Gan-Lin Zhang (Science of The Total Environment, 2024)

Cypermethrin induces Sertoli cell apoptosis through endoplasmic reticulum-mitochondrial coupling involving IP3R1-GRP75-VDAC1 - Rui Zhang; Xu-Xu Wang; Jia-fei Xie; Ting-ting Yao; Qian-wen Guo; Qi Wang; Zhen Ding; Jin-Peng Zhang; Mei-Rong Zhang; Li-Chun Xu (Reproductive Toxicology, 2024)

Behavioral and molecular response of the insect parasitic nematode Steinernema carpocapsae to plant volatiles - Peng-hua Bai; Jin-Ping Yu; Rui-rui Hu; Qian-wen Fu; Hai-chao Wu; Xing-yue Li; Guo-hao Zu; Bao-sheng Liu; Yu Zhang (Journal of Invertebrate Pathology, 2024)

Recovery hydrotalcite from neutralization sludge of acid mine drainage with high manganese for degradation of norfloxacin with activated peroxymonosulfate - Qingsheng Xu; Zhengbo Yue; Rui Deng; Kang Su; Xin Chuai; Kai Zhang; Jin Wang (Chemical Engineering Journal, 2024)

Moment Tensor and Stress Field Inversions of Mining-Induced Seismicity in A Thick-Hard Roof Zone - Chun-Hui Song; Cai-Ping Lu; Hai-Quan Liu; Jie-Fang Song; Cheng-Yu Liu; Hua-Wei Cui; Jin-Rui Zhang (Rock Mechanics and Rock Engineering, 2024)

Stereoselective cardiotoxic effects of metconazole on zebrafish (Danio rerio) based on AGE-RAGE signalling pathway - Minmin Li; Lin Yang; Rui Wang; Lin Li; Yifan Zhang; Long Li; Nuo Jin; Yatao Huang; Zhiqiang Kong; Frédéric Francis; Bei Fan; Fengzhong Wang (Science of The Total Environment, 2024)

PD-L1 expression guidance on sintilimab versus pembrolizumab with or without platinum-doublet chemotherapy in untreated patients with advanced non-small cell lung cancer (CTONG1901): A phase 2, randomized, controlled trial - Si-Yang Maggie Liu; Jie Huang; Jia-Yi Deng; Chong-Rui Xu; Hong-Hong Yan; Ming-Yi Yang; Yang-Si Li; E-E Ke; Ming-Ying Zheng; Zhen Wang; Jia-Xin Lin; Bin Gan; et al. (Science Bulletin, 2024)

Two new monoterpenoids from the roots of Paeonia lactiflora and their neuroprotective activities - Bo Fu; Jin-Ling Zhang; Xin Meng; Jia-Tong Wu; Yan Liu; Yu-Qing Wang; Yi-Qiang Zhang; Juan Pan; Wei Guan; Rui-Feng Fan; Anam Naseem; Hai-Xue Kuang; et al. (Phytochemistry Letters, 2024)

Fe-MOFs/CuS nanocomposite-mediated peroxymonosulfate activation for tetracycline degradation: Boosted dual redox cycles - Rui Ma; Zhijie Chen; Weihang Xu; Ran Yu; Yichu Zhang; Fan Chen; Xiaoming Peng; Bing-Jie Ni; Jin Qian (Journal of Cleaner Production, 2024)

Meteorological to Agricultural Drought Propagation Time Analysis and Driving Factors Recognition Considering Time-Variant Characteristics - Chengguo Wu; Yin Xu; Juliang Jin; Yuliang Zhou; Boyu Nie; Rui Li; Yi Cui; Fei Tong; Libing Zhang (Water Resources Management, 2024)

The Community of Arbuscular Mycorrhizal Fungi in Sugarcane Rhizosphere Soils in Guangxi, China - Jin-Lian Zhang; Juan Song; Yi-Hao Kang; Yun-Ying Wen; Ying-Jie Nong; Qian Wang; Xiao-Juan Qin; Ting-Su Chen; Yang-Rui Li (Sugar Tech, 2024)

Progress in the Application of Microneedles in Eye Disorders and the Proposal of the Upgraded Microneedle with Spinule - Qiannan Yang; Tingting Zhang; Yujie Wu; Qianyue Liang; Wanqi Zhao; Rui Liu; Xin Jin (Pharmaceutical Research, 2024)

A Novel Kunitz-Type Serine Protease Inhibitor (HcKuSPI) is Involved in Antibacterial Defense in Innate Immunity and Participates in Shell Formation of Hyriopsis cumingii - Can Jin; Kang Cheng; Rui Jiang; Yihang Zhang; Wen Luo (Marine Biotechnology, 2024)

Heavy Metal Scavenger Metallothionein Rescues Against Cold Stress-Evoked Myocardial Contractile Anomalies Through Regulation of Mitophagy - Zhaohui Pei; Yayuan Xiong; Shasha Jiang; Rui Guo; Wei Jin; Jun Tao; Zhenzhong Zhang; Yingmei Zhang; Yunzeng Zou; Yan Gong; Jun Ren (Cardiovascular Toxicology, 2024)

Dietary selenium levels affect mineral absorbability, rumen fermentation, microbial composition and metabolites of the grazing sheep - Lingbo Meng; Xiwei Jin; Wenxi Song; Rui Zhang; Mengjie Tong; Zhi Qi; Lan Mi (Animal Feed Science and Technology, 2024)

High-density lipoprotein cholesterol is associated with lowered cognitive recovery among acute ischemic stroke patients with mild cognitive impairment - Rui Wang; Zhuomin Jiao; Anxin Wang; Yijun Zhang; Xiangxiang Hong; Shan Huang; Jin Fu; Yinglian Zhou; Yifei Wang; Chunyang Li; Yue Liu; Ke Wei; et al. (Acta Neurologica Belgica, 2024)

Diversified cropping systems with complementary root growth strategies improve crop adaptation to and remediation of hostile soils - Wei-Ping Zhang; Surigaoge Surigaoge; Hao Yang; Rui-Peng Yu; Jin-Pu Wu; Yi Xing; Yinglong Chen; Long Li (Plant and Soil, 2024)

Synergistic effects of adsorption and chemical reduction towards the effective Cr(VI) removal in the presence of the sulfur-doped biochar material - Rui Ma; Xiangning Xu; Yichu Zhang; Dandan Zhang; Guoping Xiang; Yongjun Chen; Jin Qian; Shouliang Yi (Environmental Science and Pollution Research, 2024)

Development and evaluation of a bivalent vaccine based on recombinant newcastle disease virus expressing infectious bursal disease virus VP2L-CH3-CH4 in SPF chickens - Wen Ying Sun; Xiao Lin Cao; Yi Xuan Wang; Xiao Chen Guo; Jin Miao Liu; Zhi Qiang Xue; Hui Juan Li; Wei Wang; Ting Ting Zhang; Qianhui Li; Rui Han Qin; Yu Han Jin; et al. (Veterinary Microbiology, 2024)

Enhanced biological phosphorus removal from wastewater and dynamics of microbial population in dual PAOs symbiosis system - Deng Ying; Zhang Kun; Kang Suqin; Zheng Yaqin; Jin Haidong; Yang Rui; Ma Juan (Journal of Water Process Engineering, 2024)

Perturbation of autophagy pathways in murine alveolar macrophage by 2D TMDCs is chalcogen-dependent - Xiaofei Zhou; Weitao Jin; Rui Zhang; Xuan Mao; Jianbo Jia; Hongyu Zhou (Journal of Environmental Sciences, 2024)

Selective solvent extraction of Cu(II) from aqueous solutions using an acyl-based thiourea: Extraction study and DFT analysis of reaction mechanism - Xiaoping Huang; Kai Jin; Ruyi Zhang; Yutao Gong; Jianxian Zeng; Rui Zhang; Yuan Liu; Jianrong Xue (Hydrometallurgy, 2024)

Identification, characterization and hypolipidemic effect of novel peptides in protein hydrolysate from Protaetia brevitarsis larvae - Zong-Qi Zhang; Xin-Rui Ren; Jin Geng; Si-Cong Chen; Qing-Lei Wang; Chun-Qin Liu; Jin-Hua Xiao; Da-Wei Huang (Food Research International, 2024)

Human activity and climate change accelerate the extinction risk to non‐human primates in China - Wen‐Bo Li; Yang Teng; Ming‐Yi Zhang; Ying Shen; Jia‐Wen Liu; Ji‐Wei Qi; Xiao‐Chen Wang; Rui‐Feng Wu; Jin‐Hua Li; Paul A. Garber; Ming Li (Global Change Biology, 2024)
Human activity and climate change affect biodiversity and cause species range shifts, contractions, and expansions. Globally, human activities and climate change have emerged as persistent threats to biodiversity, leading to approximately 68% of the ~522 primate species being threatened with extinction. Here, we used habitat suitability models and integrated data on human population density, gross domestic product (GDP), road construction, the normalized difference vegetation index (NDVI), the location of protected areas (PAs), and climate change to predict potential changes in the distributional range and richness of 26 China's primate species. Our results indicate that both PAs and NDVI have a positive impact on primate distributions. With increasing anthropogenic pressure, species' ranges were restricted to areas of high vegetation cover and in PAs surrounded by buffer zones of 2.7–4.5 km and a core area of PAs at least 0.1–0.5 km from the closest edge of the PA. Areas with a GDP below the Chinese national average of 100,000 yuan were found to be ecologically vulnerable, and this had a negative impact on primate distributions. Changes in temperature and precipitation were also significant contributors to a reduction in the range of primate species. Under the expected influence of climate change over the next 30–50 years, we found that highly suitable habitat for primates will continue to decrease and species will be restricted to smaller and more peripheral parts of their current range. Areas of high primate diversity are expected to lose from 3 to 7 species. We recommend that immediate action be taken, including expanding China's National Park Program, the Ecological Conservation Redline Program, and the Natural Forest Protection Program, along with a stronger national policy promoting alternative/sustainable livelihoods for people in the local communities adjacent to primate ranges, to offset the detrimental effects of anthropogenic activities and climate change on primate survivorship.

Identification and prediction of hydrate–slug flow to improve safety and efficiency of deepwater hydrocarbon transportation - Jiguang Wang; Qian Zhang; Rui Jin; Lunxiang Zhang; Yang Meng; Haiyuan Yao; Lei Yang; Jiafei Zhao; Yongchen Song (Journal of Cleaner Production, 2023)

CeO2 nanorods with bifunctional oxygen vacancies for promoting low-pressure photothermocatalytic CO2 conversion with CH3OH to dimethyl carbonate - Shanbiao Jin; Xiushuai Guan; Xiaochao Zhang; Changming Zhang; Jianxin Liu; Yawen Wang; Yunfang Wang; Rui Li; Zhong Li; Caimei Fan (Journal of Environmental Chemical Engineering, 2023)

Effects of Mixed Cropping on Sugarcane Growth and the Community of Arbuscular Mycorrhizal Fungi - Ying-Jie Nong; Qian Wang; Juan Song; Jin-Lian Zhang; Xiao-Juan Qin; Yi-Hao Kang; Xiang-Hua Wei; Ting-Su Chen; Yang-Rui Li (Sugar Tech, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Insights into brain perceptions of the different taste qualities and hedonic valence of food via scalp electroencephalogram - Tianyi Yang; Peng Zhang; Lidong Xing; Jin Hu; Rui Feng; Junjie Zhong; Weitao Li; Yizhi Zhang; Qiaoqiao Zhu; Yamin Yang; Fan Gao; Zhiyu Qian (Food Research International, 2023)

Molecular insights of condensate trapping mechanism in shale oil reservoirs and its implications on lean gas enhanced oil recovery - Shihao Wang; Hongwei Zhang; Bikai Jin; Rui Qiao; Xian-Huan Wen (Chemical Engineering Journal, 2023)

Constructing MoS2-SnS heterostructures on N-doped carbon nanosheets for enhanced catalytic conversion of polysulfides in lithium-sulfur batteries - Junpu Zhang; Wen Xi; Feng Yu; Youfang Zhang; Rui Wang; Yansheng Gong; Beibei He; Huanwen Wang; Jun Jin (Chemical Engineering Journal, 2023)

Glutathione Might Attenuate Arsenic-Induced Liver Injury by Modulating the Foxa2-XIAP Axis to Reduce Oxidative Stress and Mitochondrial Apoptosis - Hua Zhang; Baiming Jin; Lele Liu; Haonan Li; Xiujuan Zheng; Mingqi Li; Rui He; Kewei Wang (Biological Trace Element Research, 2023)

Investigation of Campbell mode with automatic calibration operated in fission chamber-based neutron flux monitoring system on EAST - Li Yang; Li-Qun Hu; Guo-Qiang Zhong; Hong-Rui Cao; Jin-Long Zhao; Yong-Qiang Zhang; Wei-Kun Chen (Annals of Nuclear Energy, 2023)

Anti-inflammatory metabolites from the fruits of Pittosporum elevaticostatum - Jun-Rui Ren; Xin-Zheng Liu; Wei-Zhen Kong; Zhao-Xuan Wang; Jin-Ming Gao; Xiu-Yun Zhang (Phytochemistry Letters, 2023)

Oxygen-exfoliated cobalt-doped C3N4 for superior Fenton-like catalysis: The accessible metal exposure and synergistic pollutant adsorption from three-dimensional layered configuration - Qi-Xin Wei; Ai-Yong Zhang; Zedong Yang; Song Hu; De-Jin Wang; Chi Zhang; Chang Liu; Rui Liu (Journal of Environmental Chemical Engineering, 2023)

Sulfur-decorated Fe/C composite synthesized from MIL-88A(Fe) for peroxymonosulfate activation towards tetracycline degradation: Multiple active sites and non-radical pathway dominated mechanism - Jin Qian; Yichu Zhang; Zhijie Chen; Ran Yu; Yin Ye; Rui Ma; Kailong Li; Lingzhen Wang; Dongqi Wang; Bing-Jie Ni (Journal of Environmental Management, 2023)

Process and mechanism of recovering layered double hydroxides (LDHs) from acid mine drainage (AMD) and synergetic removal of manganese - Qingsheng Xu; Zhengbo Yue; Rui Deng; Xinquan Wang; Xin Chuai; Kai Zhang; Jin Wang (Journal of Environmental Chemical Engineering, 2023)

Polyamide/UiO-66-NH2 nanocomposite membranes by polyphenol interfacial engineering for molybdenum(VI) removal - Zhenwei Wu; Jianxian Zeng; Zhengqiu Yuan; Rui Zhang; Xiaoping Huang; Fan Feng; Minjuan Chen; Kai Jin; Shengkai Yang; Yahong Li (Desalination, 2023)

Orbitally-paced coastal sedimentary records and global sea-level changes in the early Permian - Ren Wei; Zhijun Jin; Rui Zhang; Mingsong Li; Yongyun Hu; Xiangwu He; Shuai Yuan (Earth and Planetary Science Letters, 2023)

Development of a novel fluorescent aptasensor based on the interaction between hexagonal β-Co(OH)2 nanoplates and nitrogen-doped carbon dots for ultrasensitive detection of patulin - Qi Sun; Zhijuan Li; Ningxin Liu; Yuting Zhou; Fuyan Zhang; Shuang Li; Peng Jin; Rui Xiang; Tao Le (Analytica Chimica Acta, 2023)

An epoxide-based covalent sensor to detect cardiac proteome aggregation in a cardio-oncology model - Hao Jin; Di Shen; Biao Jing; Zhenduo Zhang; Zhiming Wang; Rui Sun; Huaiyue Zhang; Jialu Sun; Haochen Lyu; Yu Liu; Lili Wang (Analytica Chimica Acta, 2023)

Relationship between Large-Scale Variability of North Pacific Waves and El Niño-Southern Oscillation - Xin Zhang; Kejian Wu; Rui Li; Shuai Zhang; Ruyan Zhang; Jin Liu; Alexander V. Babanin (Journal of Marine Science and Engineering, 2023)
Ocean waves are crucial for driving various oceanic processes. In this study, the spatial and temporal distribution of significant wave height (SWH) in the North Pacific (NP) is analyzed using the 42-year ERA5 reanalysis dataset from European Centre for Medium-Range Weather Forecasts (ECMWF). The presence of an ENSO signal is confirmed in wave fields of the North Pacific. Furthermore, the spatial distributions of swells and wind waves are analyzed using the Empirical Orthogonal Function (EOF) method, revealing that waves can transport large-scale signals from the NP to lower latitudes through swells. In addition, our research reveals a relationship between ENSO and Stokes drift in the NP. Stokes drift contributes positively to the maintenance of stable sea surface temperatures (SSTs) by transporting more (less) water towards the equatorial Pacific during El Niño (La Niña year) years. It is further noted that during strong ENSO events, the strength of the Stokes drift anomaly intensifies accordingly, which implies a strong link between wave-induced transport and ENSO.

Farmers’ participation into the recovery of waste agricultural plastic film: An application of the Theory of Planned Behavior - Ze-Ying Zhao; Wen-Bo Li; Peng-Yang Wang; Hong-Yan Tao; Rui Zhou; Jin-Ying Cui; Jian Zhang; Tao Tian; Xu-Zhe Zhao; Yi-Bo Wang; You-Cai Xiong (Waste Management, 2023)

Damage detection of foundation pile in high-pile wharf based on statistical high-order moment of dynamic response under regular wave excitation - Rui-hu Zhu; Qi-ming Wang; Jin-hai Zheng; Hai-kun Zeng; Jia-bao Zhang; Yan Hu; Cheng-ming Li (Ocean Engineering, 2023)

Long-term periodicity of sedimentary basins in response to astronomical forcing: Review and perspective - Rui Zhang; Zhijun Jin; Mingsong Li; Michael Gillman; Shuping Chen; Quanyou Liu; Ren Wei; Juye Shi (Earth-Science Reviews, 2023)

Resveratrol plays an anti-fibrotic and anti-autophagy role by stimulating miR-192-5p expression in urethral fibrosis - Jin Lv; Rui Zhang; DaoYuan Li; Yan Liu (Functional & Integrative Genomics, 2023)

Long-term mowing and burning have more of an effect on soil fungal communities than on bacteria in a semiarid sandy land - Jin Zhan; Yulin Li; Hongling Yang; Zhiying Ning; Lilong Wang; Rui Zhang (Applied Soil Ecology, 2023)

Hepatoprotective effects of chlorogenic acid on mice exposed to aflatoxin B1: Modulation of oxidative stress and inflammation - Kang Cheng; Jingyi Niu; Jinyan Zhang; Yining Qiao; Guorun Dong; Rui Guo; Xiaotong Zheng; Zhihua Song; Jin Huang; Jinrong Wang; Yong Zhang (Toxicon, 2023)

Soil acidification in a tailing area of ionic rare earth in Southeast China - Zhe Xu; Jin-ling Yang; Yue Zhao; Rui Hao; Gan-lin Zhang (Science of The Total Environment, 2023)

Formation of giant copper deposits in Tibet driven by tearing of the subducted Indian plate - Zengqian Hou; Rui Wang; Haijiang Zhang; Yuanchuan Zheng; Sheng Jin; Hans Thybo; Roberto F. Weinberg; Bo Xu; Zhiming Yang; Ao-Wei Hao; Lei Gao; Letian Zhang (Earth-Science Reviews, 2023)

Hierarchical Co-Fe layered double hydroxides (LDH)/Ni foam composite as a recyclable peroxymonosulfate activator towards monomethylhydrazine degradation: Enhanced electron transfer and 1O2 dominated non-radical pathway - Jin Qian; Rui Ma; Zhijie Chen; Gen Wang; Yichu Zhang; Yufei Du; Yongjun Chen; Taicheng An; Bing-Jie Ni (Chemical Engineering Journal, 2023)

Norethindrone suppress the germ cell development via androgen receptor resulting in male bias - Xiao-Bing Long; Wen-Jun Shi; Chong-Rui Yao; Si-Ying Li; Jin-Ge Zhang; Zhi-Jie Lu; Dong-Dong Ma; Yu-Xia Jiang; Guang-Guo Ying (Aquatic Toxicology, 2023)

Specific pupylation as IDEntity reporter (SPIDER) for the identification of protein-biomolecule interactions - He-Wei Jiang; Hong Chen; Yun-Xiao Zheng; Xue-Ning Wang; Qingfeng Meng; Jin Xie; Jiong Zhang; ChangSheng Zhang; Zhao-Wei Xu; Zi-Qing Chen; Lei Wang; Wei-Sha Kong; et al. (Science China Life Sciences, 2023)

International Nuclear Medicine Consensus on the Clinical Use of Amyloid Positron Emission Tomography in Alzheimer’s Disease - Mei Tian; Chuantao Zuo; Ali Cahid Civelek; Ignasi Carrio; Yasuyoshi Watanabe; Keon Wook Kang; Koji Murakami; Valentina Garibotto; John O. Prior; Henryk Barthel; Yihui Guan; Jiaying Lu; et al. (Phenomics, 2023)
Alzheimer’s disease (AD) is the main cause of dementia, with its diagnosis and management remaining challenging. Amyloid positron emission tomography (PET) has become increasingly important in medical practice for patients with AD. To integrate and update previous guidelines in the field, a task group of experts of several disciplines from multiple countries was assembled, and they revised and approved the content related to the application of amyloid PET in the medical settings of cognitively impaired individuals, focusing on clinical scenarios, patient preparation, administered activities, as well as image acquisition, processing, interpretation and reporting. In addition, expert opinions, practices, and protocols of prominent research institutions performing research on amyloid PET of dementia are integrated. With the increasing availability of amyloid PET imaging, a complete and standard pipeline for the entire examination process is essential for clinical practice. This international consensus and practice guideline will help to promote proper clinical use of amyloid PET imaging in patients with AD.

Neurodevelopmental effects of maternal folic acid supplementation: a systematic review and meta-analysis - Hanxiao Chen; Lang Qin; Rui Gao; Xiaolei Jin; Kemin Cheng; Sirui Zhang; Xiao Hu; Wenming Xu; Hongjing Wang (Critical Reviews in Food Science and Nutrition, 2023)

Application of Clostridium butyricum, Rummeliibacillus suwonensis, and Issatchenkia orientalis for Nongxiangxing baijiu fermentation: Improves the microbial communities and flavor of upper fermented grain - Tongwei Guan; Xiaotian Wu; Rui Hou; Lei Tian; Qiao Huang; Fan Zhao; Ying Liu; Shirong Jiao; Shuangquan Xiang; Jiaxu Zhang; Dong Li; Jing Luo; et al. (Food Research International, 2023)

Obliquity forcing of continental aquifers during the late Paleozoic ice age - Ren Wei; Mingsong Li; Rui Zhang; Yongyun Hu; James G. Ogg; Guoyong Liu; He Huang; Xiangwu He; Shuai Yuan; Qifan Lin; Zhijun Jin (Earth and Planetary Science Letters, 2023)

One-dimensional self-weight consolidation of layered soil under variable load and semi-permeable boundary condition - Hong-Xin Chen; Shi-Jin Feng; Zhang-Wen Zhu; Liang Gao; Zhang-Long Chen; Shu-Rui Wang (Computers and Geotechnics, 2023)

Control of chemical and microbial pollutants in liquid-solid phases of sewer pipes by Fe(II)-activated persulfate: Performance and mechanism of simultaneous removal - Jinsuo Lu; Hang Zhao; Zhiqiang Zhang; Feng Jin; Heliang Pang; Jing Yang; Xuan Wang; Rui Chen (Chemical Engineering Journal, 2023)

The intramolecular integration of carbonyl and N-nitroamino groups to effectively balance the energy and sensitivity of N-nitroamino-functionalized bisazoles - Jinxiong Cai; Jinya Zhang; Jin Xiong; Rui Li; Teng Fei; Qi Lai; Ping Yin; Siping Pang (Chemical Engineering Journal, 2023)

Emerging poly- and perfluoroalkyl substances in water and sediment from Qiantang River-Hangzhou Bay - Haixiang Cheng; Hangbiao Jin; Bin Lu; Chenhan Lv; Yinghui Ji; Hui Zhang; Rui Fan; Nan Zhao (Science of The Total Environment, 2023)

Efficient emerging contaminants (EM) decomposition via peroxymonosulfate (PMS) activation by Co3O4/carbonized polyaniline (CPANI) composite: Characterization of tetracycline (TC) degradation property and application for the remediation of EM-polluted water body - Jin Qian; Xiaohui Mi; Zhijie Chen; Weihang Xu; Wen Liu; Rui Ma; Yichu Zhang; Yufei Du; Bing-Jie Ni (Journal of Cleaner Production, 2023)

Can shallow-incorporated organic mulching replace plastic film mulching for irrigated maize production systems in arid environments? - Ze-Ying Zhao; Peng-Yang Wang; Xiao-Bin Xiong; Rui Zhou; Ying Zhu; Yi-Bo Wang; Ning Wang; Kiprotich Wesly; Wei Xue; Jing Cao; Jin-Lin Zhang; Hong-Yan Tao; et al. (Field Crops Research, 2023)

Novel adsorbent synthesized from red mud and acid mine drainage for enhanced contaminant removal: Industrial waste transformation, adsorbent performance and metal(loid) removal mechanisms - Duo-Rui Zhang; Hong-Rui Chen; Jin-Lan Xia; Zhen-Yuan Nie; Xiao-Juan Zhao; Eva Pakostova (Chemical Engineering Journal, 2023)

ZNRF2 as an oncogene is transcriptionally regulated by CREB1 in breast cancer models - Jin-Tao Liu; Zhen-Xuan Sun; Rui Zhong; Yi-Dan Zhang; Teng Wang; Yu-Dong Hou; Jian-Heng Bao; Lei Zhang; Bo Chen (Human Cell, 2023)

Photo-assisted thermal catalysis for methanol synthesis from methane oxidation on Cu-MOR/g-C3N4 - Yan-Qun Chen; Rui-Xin Zhang; Miao Ren; Ya-Xin Jin; Wen-Jing Wang; Jia-Yao Feng; Zhi-Hua Gao; Zhi-Feng Yan; Yi-Ming Liu; Wei Huang; Lei Liu; Zhi-Jun Zuo (Fuel, 2023)

Increased hypertension risk for the elderly with high blood levels of strontium and lead - Jiebao Zhang; Chunfang Xu; Yan Guo; Xingyi Jin; Zi Cheng; Qi Tao; Lin Liu; Rui Zhan; Xuemin Yu; Hongjuan Cao; Fangbiao Tao; Jie Sheng; et al. (Environmental Geochemistry and Health, 2023)

Hcprismatin-14 of Hyriopsis cumingii, a novel matrix protein is crucial for framework recognition and crystal deposition during prismatic layer formation - Can Jin; Yihang Zhang; Kang Cheng; Rui Jiang; Shangning Jiang; Yezhong Shi; Gang Ren; Wen Luo (Frontiers in Marine Science, 2023)
Mollusk shells are characterized by hierarchical aggregation of calcium carbonate and organic matrix, and matrix protein is considered as a key active ingredient to understand shell biomineralization. In this study, a total of 21 proteins, including a novel matrix protein Hcprismatin-14 were identified in the EDTA-soluble matrix of the prismatic layer of the mussel Hyriopsis cumingii by liquid chromatography tandem mass spectrometry (LC-MS/MS). The full length of Hcprismatin-14 cDNA was cloned from the mantle of H. cumingii . Hcprismatin-14 contains a high proportion of Gly, Tyr, Arg and Asp residues, their concentrated distribution forms three structurally characteristic regions: a Gly/Tyr-rich region, a WDD-repeat region and a C-terminal basic tail. Hcprismatin-14 expression was high in mantle edge tissue in a tissue-specific analysis, and during disordered crystal deposition in a saibo transplantation assay. Knocking down Hcprismatin-14 expression with double-stranded RNA induced subgrains deposition inhibition and lost contact with chitinous scaffold. In addition, the WDD-repeat region polypeptide was involved in morphological regulation of calcite and had dose-dependent inhibitory activity against aragonite deposition in vitro . Based on these results, Hcprismatin-14 appears to be a dual-function prismatic-layer matrix protein, responsible for both framework recognition and crystal deposition. These findings contribute to understanding the relationship between the modular structure of matrix protein and their regulation mechanism during shell biomineralization in mollusks.

Obliquity forcing of lake-level changes and organic carbon burial during the Late Paleozoic Ice Age - Ren Wei; Rui Zhang; Mingsong Li; Xiaojun Wang; Zhijun Jin (Global and Planetary Change, 2023)

Highly stability Cu+ species in hollow Cu2O nanoreactors by modulating cavity size for CO2 electroreduction to C2+ products - Rui Zhang; Feifei Chen; Haokun Jin; Yong Zhang; Xiaoya Hao; Yingda Liu; Tianming Feng; Xinghua Zhang; Zunming Lu; Weihua Wang; Feng Lu; Hong Dong; et al. (Chemical Engineering Journal, 2023)

An in-situ strategy to construct uracil-conjugated covalent organic frameworks with tunable fluorescence/recognition characteristics for sensitive and selective Mercury(II) detection - Xi-Rui Deng; A-Wei Hu; Sheng-Qian Hu; Wen-Li Yang; Chen Sun; Sai-Jin Xiao; Gui-Ping Yang; Qiong-Qing Zheng; Ru-Ping Liang; Li Zhang; Jian-Ding Qiu (Analytica Chimica Acta, 2023)

Creation of intermuscular bone-free mutants in amphitriploid gibel carp by editing two duplicated runx2b homeologs - Rui-Hai Gan; Zhi Li; Zhong-Wei Wang; Xi-Yin Li; Yang Wang; Xiao-Juan Zhang; Jin-Feng Tong; Yue Wu; Ling-Yun Xia; Ze-Xia Gao; Li Zhou; Jian-Fang Gui (Aquaculture, 2023)

Two pathways drive enhanced nitrogen acquisition via a complementarity effect in long-term intercropping - Yi Xing; Rui-Peng Yu; Ran An; Ning Yang; Jin-Pu Wu; Huai-Ying Ma; Jiu-Dong Zhang; Xing-Guo Bao; Hans Lambers; Long Li (Field Crops Research, 2023)

Effects of Alpine Grassland Degradation on Soil Microbial Communities in Qilian Mountains of China - Chunming Li; Derong Zhang; Gengchun Xu; Rui Yan; Yang Huang; Liuqing Feng; Jin Yi; Xiangyu Xue; Huixia Liu (Journal of Soil Science and Plant Nutrition, 2023)

Effects of social capital on farmers’ choices of climate change adaptation behavior in Dazu District, China - Lin Li; Jianjun Jin; Rui He; Foyuan Kuang; Chenyang Zhang; Xin Qiu (Climate and Development, 2023)

Case-driven assessment of power grid emergency response capability considering typhoon disaster scenario diversity - Zhao-ge Liu; Xiang-yang Li; Dilawar Khan Durrani; Rui-jin Zhang (Journal of Cleaner Production, 2023)

Z- scheme heterojunction of BiOI nanosheets grown in situ on NH2-UiO-66 crystals with rapid degradation of BPA in real water - Rui Ji; Zhuzhu Zhang; Lechen Tian; Liujun Jin; Qingfeng Xu; Jianmei Lu (Chemical Engineering Journal, 2023)

Long-term cycles of the Solar System concealed in the Mesozoic sedimentary basin record - Rui Zhang; Zhijun Jin; Michael Gillman; Quanyou Liu; Ren Wei; Peng Li; Zhihui Zhang (Science China Earth Sciences, 2023)

Plastome evolution and phylogenomics of Impatiens (Balsaminaceae) - He Qiu; Zhi-Hui Zhang; Mei-Zhen Wang; Xin-Jie Jin; Jie-Dong Lin; Hans Peter Comes; Jing-Xuan Chen; Rui-Ning Cui; Ru-Qing Duan; Pan Li (Planta, 2023)

Bicarbonate enhanced heterogeneous activation of peroxymonosulfate by copper ferrite nanoparticles for the efficient degradation of refractory organic contaminants in water - Chun Cai; Yangfan Liu; Rui Xu; Jiaheng Zhou; Jin Zhang; Yu Chen; Lingyu Liu; Lexiang Zhang; Shuping Kang; Xianjun Xie (Chemosphere, 2023)

Salicylic acid enhances the resistance of Neoporphyra haitanensis to pathogen Vibrio mediterranei 117-T6 - Shanshan Zhu; Zhen Jin; Juanjuan Chen; Rui Yang; Qijun Luo; Tiegan Wang; Peng Zhang; Haimin Chen (Aquaculture, 2023)

HIF-1α promotes paraquat induced acute lung injury and implicates a role NF-κB and Rac2 activity - Yong Zhu; Xiaoxiao Meng; Wenyu Yang; Jinfeng Wang; Jiaxiang Zhang; Rui Tian; Ruilan Wang; Qi Su; Wei Jin (Toxicology, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

New insights into lincomycin biodegradation by Conexibacter sp. LD01: Genomics characterization, biodegradation kinetics and pathways - Huaxin Lei; Jiayu Zhang; Jin Huang; Dengjin Shen; Yin Li; Rui Jiao; Renxin Zhao; Xiaoyan Li; Lin Lin; Bing Li (Journal of Hazardous Materials, 2023)

Composite organic amendment boosts soil remediation and Cd detoxification to rape under different nitrogen level - Xu Zhang; Qingkai Guan; Linghui Kong; Rui Yang; Xuesheng Liu; Juanjuan Qu; Yu Jin (European Journal of Soil Biology, 2023)

Rural residents' climate change perceptions, personal experiences, and purchase intention–behavior gap in energy-saving refrigeration appliances in Southwest China - Rui He; Jianjun Jin; Xin Qiu; Chenyang Zhang; Jubo Yan (Environmental Impact Assessment Review, 2023)

Solar ring mission: Building a panorama of the Sun and inner-heliosphere - Yuming Wang; Xianyong Bai; Changyong Chen; Linjie Chen; Xin Cheng; Lei Deng; Linhua Deng; Yuanyong Deng; Li Feng; Tingyu Gou; Jingnan Guo; Yang Guo; et al. (Advances in Space Research, 2023)

Efficacy and Safety of Recombinant Human Prourokinase in Acute Ischemic Stroke: A Phase IIa Randomized Clinical Trial - Haiqing Song; Yuan Wang; Qingfeng Ma; Huisheng Chen; Bo Liu; Yi Yang; Jianguo Zhu; Shigang Zhao; Xiaoping Jin; Yongqiu Li; Yanyong Wang; Runxiu Zhu; et al. (Translational Stroke Research, 2022)

Long-term dietary restriction ameliorates ageing-related renal fibrosis in male mice by normalizing mitochondrial functions and autophagy - Chun-Hsien Chiang; Sin-Jin Li; Ting-Rui Zhang; Ching-Yi Chen (Biogerontology, 2022)

Synthesis of graphene oxide grafted by diazanyl groups and its application in recovery of lead from lead-acid wastewater - Chao-Zhi Zhang; Rui-Hua Jin; Qian-Qian Shen; Ling-Ling Liu (Environmental Science and Pollution Research, 2022)

Comparison of horizontal wind observed by wind profiler radars with ERA5 reanalysis data in Anhui, China - Xueliang Deng; Dongyan He; Guangyuan Zhang; Song Zhu; Rui Dai; Xiaolong Jin; Wei Fu; Weiwei Shen; Jian Chen; Yuxiang Fan; Chunxuan Wei; Xin Li (Theoretical and Applied Climatology, 2022)

Nitrogen repression of deoxynivalenol biosynthesis is mediated by Mep2 ammonium permease in Fusarium graminearum - Yuting Hu; Rui Hou; Zeyi Wang; Weiwei Zhang; Jin‐Rong Xu (Environmental Microbiology, 2022)
Fusarium graminearum is an important wheat pathogen and a producer of deoxynivalenol (DON). Biosynthesis of DON is suppressed by ammonium and induced by arginine and polyamines. To better understand ammonium repression of DON biosynthesis, in this study, we functionally characterized three ammonium permease ( MEP ) genes in F. graminearum . All the mep deletion mutants were normal in growth on V8 agar. Whereas deletion of MEP1 had no detectable phenotypes, the mep2 and mep3 mutants had defects in hyphal growth under ammonium limiting conditions and infection of wheat heads, with the latter having less severe defects. Deletion of MEP2 but not MEP3 affected nitrogen repression of DON biosynthesis and genes involved in nitrate metabolism. The mep2 mep3 double mutant had more severe defects in nitrogen repression than the mep2 mutant and was defective in ascospore releasing. Mutant alleles of MEP2 with truncated C‐terminal cytoplasmic tail (CT) failed to complement the mep2 mutant. Expression of a dominant active allele of RAS2 partially rescued the defects of mep2 in nitrogen repression. Taken together, these results suggest that Mep2 acts as the major sensor of ammonium availability in F. graminearum and its CT region functions in nitrogen repression via RAS2 and downstream signalling pathways.

Surrogacy of bird species in systematic conservation planning and conservation assessments in Yunnan Province, China - Jian Zhou; Fei-ling Yang; Zi-jie Zhong; Ji Zhang; Xian Leng; Jin Ye; Rui-dong Wu (Journal of Mountain Science, 2022)

Spatial-temporal distribution and tectonic setting of Mesozoic W-mineralized granitoids in the Xing-Meng Orogenic Belt, NE China - Wei Xie; Qing-Dong Zeng; Rui-Liang Wang; Jin-Jian Wu; Zhe-Ming Zhang; Feng-Chun Li; Zhuang Zhang (International Geology Review, 2022)

RIG-I acts as a tumor suppressor in melanoma via regulating the activation of the MKK/p38MAPK signaling pathway - Rui Guo; Shun-Yuan Lu; Jin-Xia Ma; Qian-Lan Wang; Lu Zhang; Ling-Yun Tang; Yan Shen; Chun-Ling Shen; Jin-Jin Wang; Li-Ming Lu; Zhu-Gang Wang; Hong-Xin Zhang (Human Cell, 2022)
Studies have indicated that RIG-I may act as a tumor suppressor and participate in the tumorigenesis of some malignant diseases. However, RIG-I induces distinct cellular responses via different downstream signaling pathways depending on the cell type. To investigate the biological function and underlying molecular mechanism of RIG-I in the tumorigenesis of melanoma, we constructed RIG-I knockout, RIG-I -overexpressing B16-F10 and RIG-I knockdown A375 melanoma cell lines, and analyzed the RIG-I-mediated change in the biological behavior of tumor cells in spontaneous and poly (I:C)-induced RIG-I activation. Cell proliferation, cell cycling, apoptosis and migration were detected by CCK-8 assay, BrdU incorporation assay, Annexin V–PI staining assay and Transwell assay, respectively. In vivo tumorigenicity was evaluated by tumor xenograft growth in nude mice and subsequently by Ki67 staining and TUNEL assays. Furthermore, Western blotting was utilized to explore the underlying mechanism of RIG-I in melanoma cells. Our data showed that RIG-I promotes apoptosis and inhibits proliferation by G1 phase cell cycle arrest in the melanoma cell lines. Mechanistically, RIG-I induced the phosphorylation of p38 MAPK and MAPK kinases MKK3 and MKK4. In conclusion, the current study demonstrated that RIG-I suppressed the development of melanoma by regulating the activity of the MKK/p38 MAPK signaling pathway, which is relevant to research on novel therapeutic targets for this malignant disease.

Otolith Marking With Strontium for Stock Assessment in Coilia nasus - Ming-Zhi Liu; Ri-jin Jiang; Hui Zhang; Fan Yang; Xia-Fang Li; Guang-Peng Feng; Rui Yin; Feng Chen (Frontiers in Marine Science, 2022)
Mass stock enhancement and release are excellent ways to recover Coilia nasus resources. However, it is challenging to evaluate stock enhancement effectively, and it is important to establish a method suitable for estimating C. nasus populations. We explored the effectiveness of marking otoliths in these fish with strontium by immersing C. nasus in hexahydrate strontium chloride solutions. We used laser ablation inductively coupled plasma mass spectrometry to measure the strontium content of otoliths and fish bodies. The larvae (40 d post hatch) were reared in five different concentrations of strontium (0, 12, 24, 48, and 60 mg/L) for 7 d, followed by treatment in non-additive water for 3 wk. The results showed that the cumulative mortality rate was not significantly different between treatment and control groups ( P >0.05), except in the group treated with 24 mg/L strontium. The swimming and feeding behaviors did not change significantly, indicating that strontium did not negatively affect survival in this species. The strontium/calcium ratios of otoliths in the control group were stable (1.78–2.32 mmol/mol), whereas those of the experimental (marked) groups ranged widely (4.47–61.02 mmol/mol). The strontium/calcium ratios increased with increasing strontium concentration, but gradually returned to baseline values, resulting in a 100% success rate of marking with strontium. Following immersion in 12 mg/L strontium, strontium levels in the body returned to normal after 24 d. In summary, a treatment of 12 mg/L strontium for 4 d was identified as viable for marking. We confirmed the feasibility of strontium marking for the mass marking and release of C. nasus . This marking method does not affect the physiology of the fish and may provide a new approach for reasonable and scientific stock assessment of C. nasus post hatch.

Spirulina platensis aqueous extracts ameliorate colonic mucosal damage and modulate gut microbiota disorder in mice with ulcerative colitis by inhibiting inflammation and oxidative stress - Jian Wang; Liqian Su; Lun Zhang; Jiali Zeng; Qingru Chen; Rui Deng; Ziyan Wang; Weidong Kuang; Xiaobao Jin; Shuiqing Gui; Yinghua Xu; Xuemei Lu (Journal of Zhejiang University-SCIENCE B, 2022)

Genome-wide analysis and expression pattern of the PIN gene family during Korla fragrant pear calyx development - Min Jin; Xin Gong; Qiang Zhang; Yan Chen; Hongyu Ma; Tianzheng Zhang; Cuiyun Wu; Rui Zhang; Qi Zhang; Shutian Tao; Jianping Bao (Acta Physiologiae Plantarum, 2022)

Two new sesquiterpenes from the rhizomes of Atractylodes macrocephala and their biological activities - Yi-Nan Zhao; Gai Gao; Jin-Lian Ma; Rui-Zhu Xu; Tao Guo; Li-Min Wu; Xin-Guang Liu; Zhi-Shen Xie; Jiang-Yan Xu; Zhen-Qiang Zhang; Pan Wang (Natural Product Research, 2022)

Genome-Wide Identification of WUSCHEL-Related Homeobox Gene Family and their Expression Analysis During Somatic Embryogenesis in Oil Palm (Elaeis guineensis) - Anni Zhang; Yinchun Li; Rajesh Yarra; Rui Li; Hongxing Cao; Longfei Jin (Tropical Plant Biology, 2022)

Nitrate runoff loss and source apportionment in a typical subtropical agricultural watershed - Yue Dong; Jin-Ling Yang; Xiao-Rui Zhao; Shun-Hua Yang; Jan Mulder; Peter Dörsch; Gan-Lin Zhang (Environmental Science and Pollution Research, 2022)

A feasible vibration measurement and active control method of reinforced concrete lightweight pier railway bridges for heavy-haul monorail trains - Ling-kun Chen; Li-zhong Jiang; Rui Li; Qiao Li; Ming Zhang; Nan Zhang; Jin-zhang Luo; Liang Ling; Sheng-yang Zhu (European Journal of Environmental and Civil Engineering, 2022)

Enhanced stripe rust resistance obtained by combining Yr30 with a widely dispersed, consistent QTL on chromosome arm 4BL - Shengjie Liu; Xiaoting Wang; Yayun Zhang; Yangang Jin; Zhonghua Xia; Mingjie Xiang; Shuo Huang; Linyi Qiao; Weijun Zheng; Qingdong Zeng; Qilin Wang; Rui Yu; et al. (Theoretical and Applied Genetics, 2022)

Organic-rich formation and hydrocarbon enrichment of lacustrine shale strata: A case study of Chang 7 Member - Quanyou Liu; Peng Li; Zhijun Jin; Yuewu Sun; Guang Hu; Dongya Zhu; Zhenkai Huang; Xinping Liang; Rui Zhang; Jiayi Liu (Science China Earth Sciences, 2022)

Three-dimensional numerical simulation of geothermal field in space—wavenumber domain - Dai Shi-Kun; Jia Jin-Rong; Qiang Jian-Ke; Chen Qing-Rui; Ling Jia-Xuan; Zhang Ying (Applied Geophysics, 2021)

Two new diterpenoids with their antiproliferative activities from the supercritical fluid extraction of Croton crassifolius root - Chao Liu; Rui-rui Zhang; Qing-lin Niu; Jing Zhang; Mu-xuan Wang; Na-na Meng; Qing Wang; Jin-yue Sun; Wen-liang Wang (Natural Product Research, 2021)

Dietary selenium requirement of coho salmon (Oncorhynchus kisutch W.) alevins - Lian-cai Du; Hai-rui Yu; Ling-yao Li; Qin Zhang; Qi Tian; Jin-qian Liu; Ling-ling Shan (Aquaculture International, 2021)

Tracing Nutrients and Organic Matter Changes in Eutrophic Wenchang (China) and Oligotrophic Krka (Croatia) Estuaries: A Comparative Study - You-You Hao; Zhuo-Yi Zhu; Fu-Tao Fang; Tihana Novak; Milan Čanković; Enis Hrustić; Zrinka Ljubešić; Ming Li; Jin-Zhou Du; Rui-Feng Zhang; Blaženka Gašparović (Frontiers in Marine Science, 2021)
Estuaries modify the concentration and composition of riverine nutrients and organic matter (OM), which eventually determine the riverine flux effect to coasts. Nutrients, organic carbon (OC), pigments, and amino acids (AAs) from the samples collected in the eutrophic Wenchang River Estuary (WRE) in China and the oligotrophic Krka River Estuary (KRE) in Croatia were analyzed in order to have a better understanding of how estuaries regulate terrestrial materials. We found a clear increase of dissolved inorganic nitrogen (DIN) concentration and its subsequent decrease due to the removal of DIN (over 100 μM) in the WRE, whereas DIN showed minor variation lengthwise in the KRE, i.e., with the salinity changes, ranging between 1.0 and 5.8 μM. The elevated algae-derived OC, dissolved organic nitrogen, and particulate AAs nitrogen suggest that the OM assimilation may explain approximately one-third of the DIN removal in the WRE, whereas in the oligotrophic KRE, such inorganic to organic transformation is not likely to be significant. Due to the prominent estuarine nitrogen removal/assimilation process, DIN/dissolved inorganic phosphorus (DIP) ratio was as high as 425 in the upper WRE under strong riverine influence, but it declined to as low as 5.4 at the mouth of WRE, that is even lower than DIN/DIP ratio at the mouth of oligotrophic KRE (12). When compared with other rivers worldwide, the Wenchang River showed high nutrients and organic carbon yields. Given the contrasting estuarine process (e.g., DIN removal) between the KRE and the WRE, apparent high nutrient yield from eutrophic rivers should be viewed with caution in ocean studies as the final impact to coastal zone could be similar to the oligotrophic rivers like the KRE.

Heterogeneity of tight sandstone reservoirs based on fractal theory: the Xu-6 member of Xujiahe Formation in Guang'an area, central Sichuan Basin - Fang Shen; Liang Yue; Ziliang Liu; Wei Yang; Kaarel Mänd; Hui Jin; Fengjie Li; Yue Zhou; Minghe Zhang; Rui Jiang (Arabian Journal of Geosciences, 2021)

Divergent Projection Patterns Revealed by Reconstruction of Individual Neurons in Orbitofrontal Cortex - Junjun Wang; Pei Sun; Xiaohua Lv; Sen Jin; Anan Li; Jianxia Kuang; Ning Li; Yadong Gang; Rui Guo; Shaoqun Zeng; Fuqiang Xu; Yu-Hui Zhang (Neuroscience Bulletin, 2021)

How can the winter North Atlantic Oscillation influence the early summer precipitation in Northeast Asia: effect of the Arctic sea ice - Peng Zhang; Zhiwei Wu; Rui Jin (Climate Dynamics, 2021)

A below-knee compression garment reduces fatigue-induced strength loss but not knee joint position sense errors - János Négyesi; Li Yin Zhang; Rui Nian Jin; Tibor Hortobágyi; Ryoichi Nagatomi (European Journal of Applied Physiology, 2021)

The Forms, Distribution, and Risk Assessment of Sulfonamide Antibiotics in the Manure–Soil–Vegetable System of Feedlot Livestock - Caixia Jin; Shan Wei; Ruilian Sun; Wei Zou; Xingli Zhang; Qixing Zhou; Rui Liu; Liuqun Huang (Bulletin of Environmental Contamination and Toxicology, 2020)

Gastrointestinal involvement of COVID-19 and potential faecal transmission of SARS-CoV-2 - Min Song; Zong-lin Li; Ye-jiang Zhou; Gang Tian; Ting Ye; Zhang-rui Zeng; Jian Deng; Hong Wan; Qing Li; Jin-bo Liu (Journal of Zhejiang University-SCIENCE B, 2020)

Alleviation of Cd phytotoxicity and enhancement of rape seedling growth by plant growth–promoting bacterium Enterobacter sp. Zm-123 - Meng Zhang; Zonghui Jin; Xu Zhang; Guoliang Wang; Rui Li; Juanjuan Qu; Yu Jin (Environmental Science and Pollution Research, 2020)

Bioaccumulation of ytterbium oxide nanoparticles insinuate oxidative stress, inflammatory, and pathological lesions in ICR mice - Muhammad Adeel; Jin Tingting; Tariq Hussain; Xiao He; Muhammad Arslan Ahmad; Muhammad Kashif Irshad; Noman Shakoor; Peng Zhang; Xie Changjian; Yi Hao; Zhang Zhiyong; Rabia Javed; et al. (Environmental Science and Pollution Research, 2020)

Intrusion of Fall Armyworm (Spodoptera frugiperda) in Sugarcane and Its Control by Drone in China - Xiu-Peng Song; Yong-Jian Liang; Xiao-Qiu Zhang; Zhen-Qiang Qin; Jin-Ju Wei; Yang-Rui Li; Jian-Ming Wu (Sugar Tech, 2020)

Effects of Spray Parameters of Drone on the Droplet Deposition in Sugarcane Canopy - Xiao-Qiu Zhang; Xiu-Peng Song; Yong-Jian Liang; Zhen-Qiang Qin; Bao-Qing Zhang; Jin-Ju Wei; Yang-Rui Li; Jian-Ming Wu (Sugar Tech, 2020)

Interferon-α2b spray inhalation did not shorten virus shedding time of SARS-CoV-2 in hospitalized patients: a preliminary matched case-control study - Shao-rui Hao; Ren Yan; Shan-yan Zhang; Jiang-shan Lian; Huan Cai; Xiao-li Zhang; Lin Zheng; Hong-yu Jia; Jian-hua Hu; Guo-dong Yu; Jue-qing Gu; Chan-yuan Ye; et al. (Journal of Zhejiang University-SCIENCE B, 2020)

Double Peaked Stress–Strain Behavior and Progressive Failure Mechanism of Encased Coal Pillars Under Uniaxial Compression - Chunwang Zhang; Zhixin Jin; Guorui Feng; Xuanmin Song; Gao Rui; Zhang yujiang (Rock Mechanics and Rock Engineering, 2020)

PDB-1 from Potentilla discolor Bunge suppresses lung cancer cell migration and invasion via FAK/Src and MAPK signaling pathways - Na-na Meng; Rui-rui Zhang; Chao Liu; Qing Wang; Xin-kun Wang; Xu Guo; Ping-ping Wang; Jin-yue Sun (Medicinal Chemistry Research, 2020)

Comparison of epidemiological and clinical characteristics of COVID-19 patients with and without Wuhan exposure - Jiang-shan Lian; Huan Cai; Shao-rui Hao; Xi Jin; Xiao-li Zhang; Lin Zheng; Hong-yu Jia; Jian-hua Hu; Shan-yan Zhang; Guo-dong Yu; Jue-qing Gu; Chan-yuan Ye; et al. (Journal of Zhejiang University-SCIENCE B, 2020)

Spent mushroom substrate combined with alkaline amendment passivates cadmium and improves soil property - Zonghui Jin; Meng Zhang; Rui Li; Xu Zhang; Guoliang Wang; Xuesheng Liu; Juanjuan Qu; Yu Jin (Environmental Science and Pollution Research, 2020)

U.S. national parks accessibility and visitation - Xing-ju Shen; Rui-hong Huang; Jin-shan Zhang (Journal of Mountain Science, 2019)

Chemical constituents from the leaves of Melia azedarach - Jin Zeng; Rui-Jing Ma; Ling Wang; Sheng-Nan Zhang; Hong-Zhi Song; Yang Yang; Qin-Gang Tan (Natural Product Research, 2019)

Application of Multi-rotor Unmanned Aerial Vehicle Application in Management of Stem Borer (Lepidoptera) in Sugarcane - Xiao-Qiu Zhang; Yong-Jian Liang; Zhen-Qiang Qin; De-Wei Li; Chun-Yan Wei; Jin-Ju Wei; Yang-Rui Li; Xiu-Peng Song (Sugar Tech, 2019)

Seedling growth and nutrition responses of two subtropical tree species to NH4+-N and NO3−-N deposition - Rui Zhang; Zhichun Zhou; Yi Wang; Guoqing Jin (New Forests, 2019)

Aspergilolide, a steroid lactone produced by an endophytic fungus Aspergillus sp . MBL1612 isolated from Paeonia ostii - Pei-Liang Zhang; Gang Wang; Feng-Qing Xu; Jin-Song Liu; Ju-Tao Wang; Rui Zhang; Hai-Tao Liu; Jiang-Miao Hu; Guo-Kai Wang; Pei-Yun Wu (Natural Product Research, 2019)

Resina draconis inhibits the endoplasmic-reticulum-induced apoptosis of myocardial cells via regulating miR-423-3p/ERK signaling pathway in a tree shrew myocardial ischemia–reperfusion model - Tian-Rui Yang; Tong Zhang; Ning-Hui Mu; Li-Bo Ruan; Jin-Lan Duan; Rong-Ping Zhang; Yun-Bo Miao (Journal of Biosciences, 2019)

Long noncoding RNA UCA1 promotes the proliferation of hypoxic human pulmonary artery smooth muscle cells - Tian-Tian Zhu; Rui-Li Sun; Ya-Ling Yin; Jin-Ping Quan; Ping Song; Jian Xu; Ming-Xiang Zhang; Peng Li (Pflügers Archiv - European Journal of Physiology, 2019)

The role of lamin A/C in mesenchymal stem cell differentiation - Bo Zhang; Yang Yang; Reziwan Keyimu; Jin Hao; Zhihe Zhao; Rui Ye (Journal of Physiology and Biochemistry, 2019)

Comparative detection of Karenia mikimotoi by exponential rolling circle amplification (E-RCA) and double-ligation E-RCA - Chunyun Zhang; Rui Sun; Yuanyuan Wang; Guofu Chen; Changlu Guo; Jin Zhou (Journal of Applied Phycology, 2019)

Cloning and Identification of Differentially Expressed Genes Associated with Smut in Sugarcane - Xiu-Peng Song; Dan-Dan Tian; Ming-Hui Chen; Zhen-Qiang Qin; Jin-Ju Wei; Chun-Yan Wei; Xiao-Qiu Zhang; De-Wei Li; Li-Tao Yang; Yang-Rui Li (Sugar Tech, 2018)

Relative Telomere Length and Stroke Risk in a Chinese Han Population - Dan Gao; Rui Zhang; Guofa Ji; Chunqi Li; Dangshe Guo; Tianbo Jin; Mingwei Chen (Journal of Molecular Neuroscience, 2018)

Tibetan Plateau capacitor effect during the summer preceding ENSO: from the Yellow River climate perspective - Rui Jin; Zhiwei Wu; Peng Zhang (Climate Dynamics, 2018)

Effects of diurnal temperature range on mortality in Hefei city, China - Jing Tang; Chang-chun Xiao; Yu-rong Li; Jun-qing Zhang; Hao-yuan Zhai; Xi-ya Geng; Rui Ding; Jin-xia Zhai (International Journal of Biometeorology, 2018)

Microsatellite records for volume 10, issue 1 - Ai-Qing Yu; Chengxin Fu; Chongbo He; Fei Liu; Guo-Hua Ding; Hongman Hou; Jian Zhao; Jianmin Yang; Jiansheng Wang; Kun-ci Chen; Lan-lan Zhang; Pan Li; et al. (Conservation Genetics Resources, 2018)

Creation of miniature pig model of human Waardenburg syndrome type 2A by ENU mutagenesis - Tang Hai; Weiwei Guo; Jing Yao; Chunwei Cao; Ailing Luo; Meng Qi; Xianlong Wang; Xiao Wang; Jiaojiao Huang; Ying Zhang; Hongyong Zhang; Dayu Wang; et al. (Human Genetics, 2017)

Thermal recovery process of a backfilled open-pit in permafrost area at the Gulian strip coal mine in Northeast China - Shu-hui Gao; Rui-xia He; Hui-jun Jin; Ya-dong Huang; Jian-ming Zhang; Dong-liang Luo (Journal of Mountain Science, 2017)

Behavioral responses of the egg parasitoid Trissolcus japonicus to volatiles from adults of its stink bug host, Halyomorpha halys - Yong-Zhi Zhong; Jin-Ping Zhang; Li-Li Ren; Rui Tang; Hai-Xia Zhan; Guo-Hua Chen; Feng Zhang (Journal of Pest Science, 2017)

Erratum to: Transposon insertion resulted in the silencing of Wx-B1n in Chinese wheat landraces - Ling‑Ling Zhang; Hu Chen; Mi Luo; Xiao‑Wei Zhang; Mei Deng; Jian Ma; Peng‑Fei Qi; Ji‑Rui Wang; Guo‑Yue Chen; Ya‑Xi Liu; Zhi‑En Pu; Wei Li; et al. (Theoretical and Applied Genetics, 2017)

Transposon insertion resulted in the silencing of Wx-B1n in Chinese wheat landraces - Ling-Ling Zhang; Hu Chen; Mi Luo; Xiao-Wei Zhang; Mei Deng; Jian Ma; Peng-Fei Qi; Ji-Rui Wang; Guo-Yue Chen; Ya-Xi Liu; Zhi-En Pu; Wei Li; et al. (Theoretical and Applied Genetics, 2017)

Assessment of Correlation Between Early and Late Efficacy Endpoints to Identify Potential Surrogacy Relationships in Non-Hodgkin Lymphoma: a Literature-Based Meta-analysis of 108 Phase II and Phase III Studies - Rui Zhu; Dan Lu; Yu-Waye Chu; Akiko Chai; Michelle Green; Nancy Zhang; Jin Yan Jin (The AAPS Journal, 2017)

Improved salt tolerance of medicinal plant Codonopsis pilosula by Bacillus amyloliquefaciens GB03 - Qing-Qing Han; Yong-Na Wu; Hui-Juan Gao; Rui Xu; Paul W. Paré; Huazhong Shi; Qi Zhao; Hui-Ru Li; Sardar Ali Khan; Yin-Quan Wang; Suo-Min Wang; Jin-Lin Zhang (Acta Physiologiae Plantarum, 2017)

Thermal state of soils in the active layer and underlain permafrost at the kilometer post 304 site along the China-Russia Crude Oil Pipeline - Yong-ping Wang; Guo-yu Li; Hui-jun Jin; Lan-zhi Lu; Rui-xia He; Peng Zhang (Journal of Mountain Science, 2016)

TRI6 and TRI10 play different roles in the regulation of deoxynivalenol (DON) production by cAMP signalling in Fusarium graminearum - Cong Jiang; Chengkang Zhang; Chunlan Wu; Panpan Sun; Rui Hou; Huiquan Liu; Chenfang Wang; Jin‐Rong Xu (Environmental Microbiology, 2016)
Summary The biosynthesis of mycotoxin deoxynivalenol (DON) in Fusarium graminearum is regulated by two pathway‐specific transcription factors Tri6 and Tri10 and affected by various host and environmental factors. In this study, we showed that cyclic adenosine monophosphate (cAMP) treatment induced DON production by stimulating TRI gene expression and DON‐associated cellular differentiation in F. graminearum . Interestingly, exogenous cAMP had no effects on the tri6 mutant but partially recovered the defect of tri10 mutant in DON biosynthesis. Although the two cAMP phosphodiesterase genes PDE1 and PDE2 had overlapping functions in vegetative growth, conidiation, sexual reproduction and plant infection, deletion of PDE2 but not PDE1 activated intracellular PKA activities and increased DON production. Whereas the tri6 pde2 mutant failed to produce DON, the tri10 pde2 double mutant produced a significantly higher level of DON than the tri10 mutant. Cellular differentiation associated with DON production was stimulated by exogenous cAMP or deletion of PDE2 in both tri10 and tri6 mutants. These data indicate that TRI6 is essential for the regulation of DON biosynthesis by cAMP signalling but elevated PKA activities could partially bypass the requirement of TRI10 for TRI gene‐expression and DON production, and Pde2 is the major cAMP phosphodiesterase to negatively regulate DON biosynthesis in F. graminearum .

Nucleus accumbens hyperpolarization-activated cyclic nucleotide-gated channels modulate methamphetamine self-administration in rats - Dan-Ni Cao; Rui Song; Shu-Zhuo Zhang; Ning Wu; Jin Li (Psychopharmacology, 2016)

ZmDBF3, a Novel Transcription Factor from Maize (Zea mays L.), Is Involved in Multiple Abiotic Stress Tolerance - Wei Zhou; Cheng-Guo Jia; Xian Wu; Rui-Xue Hu; Gang Yu; Xiang-Hui Zhang; Jin-Liang Liu; Hong-Yu Pan (Plant Molecular Biology Reporter, 2016)

Circulation and in vivo distribution of duck hepatitis A virus types 1 and 3 in infected ducklings - Shao-Li Lin; Ri-Chao Cong; Rui-Hua Zhang; Jun-Hao Chen; Lin-Lin Xia; Zhi-Jing Xie; Yu Wang; Yan-Li Zhu; Shi-Jin Jiang (Archives of Virology, 2016)

Ectopic expression of UGT75D1, a glycosyltransferase preferring indole-3-butyric acid, modulates cotyledon development and stress tolerance in seed germination of Arabidopsis thaliana - Gui-Zhi Zhang; Shang-Hui Jin; Xiao-Yi Jiang; Rui-Rui Dong; Pan Li; Yan-Jie Li; Bing-Kai Hou (Plant Molecular Biology, 2016)

Systematic Review by Multivariate Meta-analyses on the Possible Role of Tumor Necrosis Factor-α Gene Polymorphisms in Association with Ischemic Stroke - Yu-Ming Niu; Hong Weng; Chao Zhang; Rui-Xia Yuan; Jin-Zhu Yan; Xiang-Yu Meng; Jie Luo (NeuroMolecular Medicine, 2015)

Purification of a novel hydrophobin PN1 involved in antibacterial activity from an edible mushroom Pleurotus nebrodensis - Rui Ying Zhang; Dan Dan Hu; Jin Gang Gu; Jin Xia Zhang; Paul H. Goodwin; Qing Xiu Hu (European Journal of Plant Pathology, 2015)

Effect of Dietary Selenomethionine Supplementation on Growth Performance, Tissue Se Concentration, and Blood Glutathione Peroxidase Activity in Kid Boer Goats - Yu-xuan Song; Jin-xing Hou; Lei Zhang; Jian-gang Wang; Xiao-rui Liu; Zhan-qin Zhou; Bin-yun Cao (Biological Trace Element Research, 2015)

MiR-1224-5p acts as a tumor suppressor by targeting CREB1 in malignant gliomas - Jin Qian; Rui Li; Ying-Yi Wang; Yan Shi; Wen-Kang Luan; Tao Tao; Jun-Xia Zhang; Yi-Chang Xu; Yong-Ping You (Molecular and Cellular Biochemistry, 2015)

The impact of the cognition of landscape experience on tourist environmental conservation behaviors - Yu-ling Zhang; Jie Zhang; Hong-Lei Zhang; Shao-wen Cheng; Yong-rui Guo; Jin-hai Ma; Jing-rong Sun (Journal of Mountain Science, 2015)

A novel species of ellipsoidal multicellular magnetotactic prokaryotes from L ake Y uehu in C hina - Yi‐Ran Chen; Rui Zhang; Hai‐Jian Du; Hong‐Miao Pan; Wen‐Yan Zhang; Ke Zhou; Jin‐Hua Li; Tian Xiao; Long‐Fei Wu (Environmental Microbiology, 2015)
Summary Two morphotypes of multicellular magnetotactic prokaryotes ( MMPs ) have been identified: spherical (several species) and ellipsoidal (previously one species). Here, we report novel ellipsoidal MMPs that are ∼ 10 × 8 μm in size, and composed of about 86 cells arranged in six to eight interlaced circles. Each MMP was composed of cells that synthesized either bullet‐shaped magnetite magnetosomes alone, or both bullet‐shaped magnetite and rectangular greigite magnetosomes. They showed north‐seeking magnetotaxis, ping‐pong motility and negative phototaxis at a velocity up to 300 μm s −1 . During reproduction, they divided along either their long‐ or short‐body axes. For genetic analysis, we sorted the ellipsoidal MMPs with micromanipulation and amplified their genomes using multiple displacement amplification. We sequenced the 16 S r RNA gene and found 6.9% sequence divergence from that of ellipsoidal MMPs , Candidatus Magnetananas tsingtaoensis and > 8.3% divergence from those of spherical MMPs . Therefore, the novel MMPs belong to different species and genus compared with the currently known ellipsoidal and spherical MMPs respectively. The novel MMPs display a morphological cell differentiation, implying a potential division of labour. These findings provide new insights into the diversity of MMPs in general, and contribute to our understanding of the evolution of multicellularity among prokaryotes.

An 18-element GEO broadcast ephemeris based on non-singular elements - Lan Du; Zhongkai Zhang; Jin Zhang; Li Liu; Rui Guo; Feng He (GPS Solutions, 2015)

Calreticulin is localized at mitochondria of rat cardiomyocytes and affected by furazolidone - Hu Shan; Jin Wei; Ming Zhang; Lin Lin; Rui Yan; Yanhe Zhu; Rong Zhang (Molecular and Cellular Biochemistry, 2014)

Two new cadinane-type sesquiterpenes from the Chinese liverwort Frullania serrata - Rui-Juan Li; Rong-Xiu Zhu; Yu Zhao; Susan L. Morris-Natschke; Chin-Ho Chen; Song Wang; Jiao-Zhen Zhang; Jin-Chuan Zhou; Hong-Xiang Lou; Kuo-Hsiung Lee (Natural Product Research, 2014)

Chemical constituents from Melastoma dodecandrum and their inhibitory activity on interleukin-8 production in HT-29 cells - Guo-Xun Yang; Rui-Ze Zhang; Bin Lou; Ke-Jun Cheng; Juan Xiong; Jin-Feng Hu (Natural Product Research, 2014)

Isolation and characterization of nineteen novel polymorphic microsatellite loci for the northern snakehead Channa argus - Ruo-Jin Yan; Kai-Jian Wei; Xiang-Zhao Guo; Gui-Rong Zhang; Jonathan P. A. Gardner; Rui-Bin Yang; Kun-Ci Chen (Conservation Genetics Resources, 2014)

Distinctive expression and cellular distribution of dopamine receptors in the pancreatic islets of rats - Ye Chen; Feng Hong; Hui Chen; Rui-Fang Fan; Xiao-Li Zhang; Yue Zhang; Jin-Xia Zhu (Cell and Tissue Research, 2014)

Isolation and characterization of twenty-three polymorphic microsatellite loci in Schizothorax macropogon - Xiang-Zhao Guo; Gui-Rong Zhang; Ruo-Jin Yan; Wei Ji; Rui-Bin Yang; Kai-Jian Wei; Deng-Qiang Wang (Conservation Genetics Resources, 2014)

Genome-Wide Identification, Classification, Expression Profiling, and SSR Marker Development of the MADS-Box Gene Family in Citrus - Xiao-Jin Hou; Sheng-Rui Liu; Muhammad Rehman Gul Khan; Chun-Gen Hu; Jin-Zhi Zhang (Plant Molecular Biology Reporter, 2014)

Effects of bromide and iodide ions on the formation of disinfection by-products during ozonation and subsequent chlorination of water containing biological source matters - Xiao-song Zha; Yan Liu; Xiang Liu; Qiang Zhang; Rui-hua Dai; Ling-wen Ying; Jin Wu; Jing-ting Wang; Luming Ma (Environmental Science and Pollution Research, 2014)

Climate change and water resources management in Tuwei river basin of Northwest China - Wang Xiao-jun; Zhang Jian-yun; Wang Jian-hua; He Rui-min; Amgad ElMahdi; Liu Jin-hua; Wang Xin-gong; David King; Shamsuddin Shahid (Mitigation and Adaptation Strategies for Global Change, 2014)

The N-glycoform of sRAGE is the key determinant for its therapeutic efficacy to attenuate injury-elicited arterial inflammation and neointimal growth - Hyun-Jin Tae; Ji Min Kim; Sungha Park; Noboru Tomiya; Geng Li; Wen Wei; Natalia Petrashevskaya; Ismayil Ahmet; John Pang; Stefanie Cruschwitz; Rebecca A. Riebe; Yinghua Zhang; et al. (Journal of Molecular Medicine, 2013)

Wip1 Phosphatase Involved in Lipopolysaccharide-Induced Neuroinflammation - Xiang Tan; Jingjing Zhang; Wei Jin; Lei Li; Wei Xu; Heyi Zheng; Ying Rui; Kaifu Ke; Ranran Zhou; Maohong Cao; Yongjin Pan (Journal of Molecular Neuroscience, 2013)

CTLA-4 polymorphisms and systemic lupus erythematosus (SLE): a meta-analysis - Jin-Xia Zhai; Li-Wei Zou; Zhao-Xiang Zhang; Wen-Jing Fan; Han-Yong Wang; Ting Liu; Zheng Ren; Rui-Xue Dai; Dongqing Ye (Molecular Biology Reports, 2013)

Evaluation of oyster mushroom strains for resistance to Pseudomonas tolaasii by inoculation in spawned substrates - Rui Ying Zhang; Dan Dan Hu; Jin Gang Gu; Xue Mei Zuo; Qing Xiu Hu; Jin Xia Zhang (European Journal of Plant Pathology, 2013)

The Effect of Energy Substrates on PHB Accumulation of Acidiphilium cryptum DX1-1 - Ai-ling Xu; Jin-lan Xia; Zhi-wen Song; Peng Jiang; Yan Xia; Min-xi Wan; Rui-yong Zhang; Yi Yang; Ke-ke Liu (Current Microbiology, 2013)

Activating transcription factor 4 is involved in endoplasmic reticulum stress-mediated apoptosis contributing to vascular calcification - Xiao-Hui Duan; Jin-Rui Chang; Jing Zhang; Bao-Hong Zhang; Yu-Lin Li; Xu Teng; Yi Zhu; Jie Du; Chao-Shu Tang; Yong-Fen Qi (Apoptosis, 2013)

Clinical and angiographic features associated with coronary collateralization in stable angina patients with chronic total occlusion - Zhen Sun; Ying Shen; Lin Lu; Rui-yan Zhang; Li-jin Pu; Qi Zhang; Zheng-kun Yang; Jian Hu; Qiu-jing Chen; Wei-feng Shen (Journal of Zhejiang University-SCIENCE B, 2013)

Peroxisome Proliferator-Activated Receptor γ Ligands Retard Cultured Vascular Smooth Muscle Cells Calcification Induced by High Glucose - Ye-Bo Zhou; Jing Zhang; Ding-Qiong Peng; Jin-Rui Chang; Yan Cai; Yan-Rong Yu; Mo-Zhi Jia; Wei Wu; You-Fei Guan; Chao-Shu Tang; Yong-Fen Qi (Cell Biochemistry and Biophysics, 2013)

Treatment with exogenous hydrogen sulfide attenuates hyperoxia-induced acute lung injury in mice - Huai-Dong Li; Zhao-Rui Zhang; Qing-Xiang Zhang; Zhi-Chu Qin; Deng-Ming He; Jin-Song Chen (European Journal of Applied Physiology, 2013)

Molecular cloning and functional analysis of a blue light receptor gene MdCRY2 from apple (Malus domestica) - Yuan-Yuan Li; Ke Mao; Cheng Zhao; Xian-Yan Zhao; Rui-Fen Zhang; Hua-Lei Zhang; Huai-Rui Shu; Yu-Jin Hao (Plant Cell Reports, 2013)

Inhibition of autophagy enhances anticancer effects of bevacizumab in hepatocarcinoma - Xian-ling Guo; Ding Li; Kai Sun; Jin Wang; Yan Liu; Jian-rui Song; Qiu-dong Zhao; Shan-shan Zhang; Wei-jie Deng; Xue Zhao; Meng-chao Wu; Li-xin Wei (Journal of Molecular Medicine, 2013)

Cytoplasmic diversity in Brassica rapa L. investigated by mitochondrial markers - Rui-Jie Zhang; Sheng-Wu Hu; Jin-Qiang Yan; Gen-Lou Sun (Genetic Resources and Crop Evolution, 2013)

Spatial patterns and climate drivers of carbon fluxes in terrestrial ecosystems of China - Gui‐Rui Yu; Xian‐Jin Zhu; Yu‐Ling Fu; Hong‐Lin He; Qiu‐Feng Wang; Xue‐Fa Wen; Xuan‐Ran Li; Lei‐Ming Zhang; Li Zhang; Wen Su; Sheng‐Gong Li; Xiao‐Min Sun; et al. (Global Change Biology, 2013)
Understanding the dynamics and underlying mechanism of carbon exchange between terrestrial ecosystems and the atmosphere is one of the key issues in global change research. In this study, we quantified the carbon fluxes in different terrestrial ecosystems in China, and analyzed their spatial variation and environmental drivers based on the long‐term observation data of China FLUX sites and the published data from other flux sites in China. The results indicate that gross ecosystem productivity ( GEP ), ecosystem respiration ( ER ), and net ecosystem productivity ( NEP ) of terrestrial ecosystems in China showed a significantly latitudinal pattern, declining linearly with the increase of latitude. However, GEP , ER , and NEP did not present a clear longitudinal pattern. The carbon sink functional areas of terrestrial ecosystems in China were mainly located in the subtropical and temperate forests, coastal wetlands in eastern China, the temperate meadow steppe in the northeast China, and the alpine meadow in eastern edge of Qinghai‐Tibetan Plateau. The forest ecosystems had stronger carbon sink than grassland ecosystems. The spatial patterns of GEP and ER in China were mainly determined by mean annual precipitation ( MAP ) and mean annual temperature ( MAT ), whereas the spatial variation in NEP was largely explained by MAT . The combined effects of MAT and MAP explained 79%, 62%, and 66% of the spatial variations in GEP , ER , and NEP , respectively. The GEP , ER , and NEP in different ecosystems in China exhibited ‘positive coupling correlation’ in their spatial patterns. Both ER and NEP were significantly correlated with GEP , with 68% of the per‐unit GEP contributed to ER and 29% to NEP . MAT and MAP affected the spatial patterns of ER and NEP mainly by their direct effects on the spatial pattern of GEP .

Effects of nitrate concentration on the denitrification potential of a calcic cambisol and its fractions of N2, N2O and NO - Rui Wang; Qi Feng; Tingting Liao; Xunhua Zheng; Klaus Butterbach-Bahl; Wei Zhang; Chunyi Jin (Plant and Soil, 2013)

The methylation of C/EBP β gene promoter and regulated by GATA-2 protein - Wan Rui; Zhang Jin; Gen Zhe; HouYan Song (Molecular Biology Reports, 2013)

Screening for significant atherosclerotic renal artery stenosis with a regression model in patients undergoing transradial coronary angiography/intervention - Li-jin Pu; Ying Shen; Rui-yan Zhang; Qi Zhang; Lin Lu; Feng-hua Ding; Jian Hu; Zheng-kun Yang; Wei-feng Shen (Journal of Zhejiang University-SCIENCE B, 2012)

Increased expression of calcium-sensing receptors in atherosclerosis confers hypersensitivity to acute myocardial infarction in rats - Jin Guo; Hong-zhu Li; Lu-chuan Wang; Wei-hua Zhang; Guang-wei Li; Wen-jing Xing; Rui Wang; Chang-qing Xu (Molecular and Cellular Biochemistry, 2012)

Polymorphisms in the XPG gene and risk of gastric cancer in Chinese populations - Jing He; Li-Xin Qiu; Meng-Yun Wang; Rui-Xi Hua; Ruo-Xin Zhang; Hong-Ping Yu; Ya-Nong Wang; Meng-Hong Sun; Xiao-Yan Zhou; Ya-Jun Yang; Jiu-Cun Wang; Li Jin; et al. (Human Genetics, 2012)

Phosphorylation of GIT1 tyrosine 321 is required for association with FAK at focal adhesions and for PDGF-activated migration of osteoblasts - Yongxin Ren; Lipeng Yu; Jin Fan; Ze Rui; Zhengzhe Hua; Zitao Zhang; Ning Zhang; Guoyong Yin (Molecular and Cellular Biochemistry, 2012)

Jeju Ground Water Containing Vanadium Enhances Antioxidant Systems in Human Liver Cells - Areum Daseul Kim; Rui Zhang; Kyoung Ah Kang; Ho Jin You; Kyung Goo Kang; Jin Won Hyun (Biological Trace Element Research, 2012)

Gene expression profiling of Sinapis alba leaves under drought stress and rewatering growth conditions with Illumina deep sequencing - Cai-Hua Dong; Chen Li; Xiao-Hong Yan; Shun-Mou Huang; Jin-Yong Huang; Li-Jun Wang; Rui-Xing Guo; Guang-Yuan Lu; Xue-Kun Zhang; Xiao-Ping Fang; Wen-Hui Wei (Molecular Biology Reports, 2012)

Development of SSR markers for typing cultivars in the mushroom Auricularia auricula-judae - Rui Ying Zhang; Dan Dan Hu; Jin Gang Gu; Qing Xiu Hu; Xue Mei Zuo; He Xiang Wang (Mycological Progress, 2012)

Purification and partial characterization of glutathione S-transferases from three field populations of Panonychus citri (Acari: Tetranychidae) - Jin-Zhi Niu; Wei Dou; Bao-Jun Wang; Guo-Na Zhang; Rui Zhang; Yi Yin; Jin-Jun Wang (Experimental and Applied Acarology, 2012)

MED19 promotes proliferation and tumorigenesis of lung cancer - Mei Sun; Rui Jiang; Jin-dong Li; Shu-li Luo; Hong-Wen Gao; Cheng-yan Jin; Dong-lei Shi; Chun-guang Wang; Bin Wang; Xing-yi Zhang (Molecular and Cellular Biochemistry, 2011)

Osteoinduction by Ca-P biomaterials implanted into the muscles of mice - Rui-na Yang; Feng Ye; Li-jia Cheng; Jin-jing Wang; Xiao-feng Lu; Yu-jun Shi; Hong-song Fan; Xing-dong Zhang; Hong Bu (Journal of Zhejiang University-SCIENCE B, 2011)

Production of Chitinase and its Optimization from a Novel Isolate Serratia marcescens XJ-01 - Jin-Lan Xia; Jing Xiong; Rui-Yong Zhang; Ke-Ke Liu; Bin Huang; Zhen-Yuan Nie (Indian Journal of Microbiology, 2011)

Effects of Copper Exposure on Expression of Glutathione-Related Genes in Acidithiobacillus ferrooxidans - Jin-lan Xia; Shun Wu; Rui-yong Zhang; Cheng-gui Zhang; Huan He; Hong-chen Jiang; Zhen-yuan Nie; Guan-zhou Qiu (Current Microbiology, 2011)

Influence of soluble microbial products (SMP) on wastewater disinfection byproducts: trihalomethanes and haloacetic acid species from the chlorination of SMP - Yuan-yuan Wei; Yan Liu; Yun Zhang; Rui-hua Dai; Xiang Liu; Jin-jian Wu; Qiang Zhang (Environmental Science and Pollution Research, 2011)

The pentapeptide PLNPK inhibits systemic lupus erythematosus-associated renal damage - Jun-qiang Lv; Wen Zhang; Song Wang; Lin Zhao; Rui Ma; Jin-wei Hu; Li-juan Wang; Jie Meng; Chun-lei Zhou; Gang Lin; Rong Lu; Zhi Yao (Inflammation Research, 2010)

The functional expression of calcium-sensing receptors in BRL cells and related signal transduction pathway responsible for intracellular calcium elevation - Wenjing Xing; Guangwei Li; Yuhui Xi; Jin Guo; Hongzhu Li; Hongxia Li; Weihua Zhang; Li Zhang; Lingyun Wu; Rui Wang; Changqing Xu (Molecular and Cellular Biochemistry, 2010)

NMDA receptor antagonist MK-801 reduces neuronal damage and preserves learning and memory in a rat model of traumatic brain injury - Rui-Zhang Han; Jin-Jia Hu; Yuan-Chi Weng; Ding-Feng Li; Yi Huang (Neuroscience Bulletin, 2009)

A novel triple-regulated oncolytic adenovirus carrying PDCD5 gene exerts potent antitumor efficacy on common human leukemic cell lines - Min Xie; Ji-Hong Niu; Yan Chang; Qi-Jun Qian; Hong-Ping Wu; Lin-Fang Li; Yao Zhang; Jin-Lan Li; Xiao-Jun Huang; Guo-Rui Ruan (Apoptosis, 2009)

Angiotensin II upregulates Toll-like receptor 4 and enhances lipopolysaccharide-induced CD40 expression in rat peritoneal mesothelial cells - Jun Wu; Xiao Yang; Yun-Fang Zhang; Shu-Feng Zhou; Rui Zhang; Xiu-Qing Dong; Jin-Jin Fan; Mei Liu; Xue-Qing Yu (Inflammation Research, 2009)

Identification of genes transcribed by Haemophilus parasuis in necrotic porcine lung through the selective capture of transcribed sequences (SCOTS) - Hui Jin; Yun Wan; Rui Zhou; Liangjun Li; Rui Luo; Sihua Zhang; Junyong Hu; Paul R. Langford; Huanchun Chen (Environmental Microbiology, 2008)
Summary Haemophilus parasuis is the aetiological agent of Glässer's disease, which has received more attention in the past decade due to the increasing economic losses in the pig industry worldwide. Little is known about the mechanisms by which H. parasuis survives in the host. In this study, selective capture of transcribed sequences (SCOTS) was used to identify H. parasuis genes upregulated in necrotic porcine lung 7 days post infection. Thirty‐eight genes were identified that were upregulated during infection of the lung tissue of pigs, compared with growth in culture medium. In two examples chosen gene expression was not confined to the lungs, there being variation between tissues. The data support biofilm formation being an important mode of growth for colonization and/or persistence. Results from the in vitro studies suggest that, as for other pathogens, iron and oxygen restriction and heat stress are important environmental signals to regulate gene expression. This study has identified genes of H. parasuis that are upregulated during infection of porcine lung tissue as compared with in vitro growth conditions.

Protective effect of butin against hydrogen peroxide-induced apoptosis by scavenging reactive oxygen species and activating antioxidant enzymes - Rui Zhang; Sungwook Chae; Kyoung Ah Kang; Mei Jing Piao; Dong Ok Ko; Zhi Hong Wang; Doek Bae Park; Jae Woo Park; Ho Jin You; Jin Won Hyun (Molecular and Cellular Biochemistry, 2008)

Survival and integration of tissue-engineered corneal stroma in a model of corneal ulcer - Chao Zhang; Xin Nie; Dan Hu; Yuan Liu; Zhihong Deng; Rui Dong; YongJie Zhang; Yan Jin (Cell and Tissue Research, 2007)

Modified Paclitaxel-loaded Nanoparticles for Inhibition of Hyperplasia in a Rabbit Arterial Balloon Injury Model - Lin Mei; Hongfan Sun; Xu Jin; Dunwan Zhu; Rui Sun; Minfang Zhang; Cunxian Song (Pharmaceutical Research, 2007)

Prohibitin suppresses renal interstitial fibroblasts proliferation and phenotypic change induced by transforming growth factor-β1 - Wei Guo; Hong Xu; Jing Chen; Yong Yang; Jia Wei Jin; Rui Fu; Hai Mei Liu; Xi Liang Zha; Zhi Gang Zhang; Wen Yan Huang (Molecular and Cellular Biochemistry, 2007)

Research progress of socio-economic water cycle in China - Jia Shao-feng; Wang Guo; Zhang Shi-feng; Yu Gui-rui; Wang Jin-xia; Xia Jun (Journal of Geographical Sciences, 2002)

New progress of research on water cycle in atmosphere in China - Wang Guo; Jia Shao-feng; Yu Gui-rui; Xu Juan; Wang Jin-xia; Wang Qiu-feng; Ge Quan-sheng; Huang Ji-kun; Xia Jun; Li Li-fnjuan; Jin De-sheng; Dong Suo-cheng; et al. (Journal of Geographical Sciences, 2001)